In the Name of Liberalism: Pierre Trudeau, Organized Labour, and the Canadian Social Democratic Left, 1949-1959 - Aivalis, Christo (Canadian Historical Review, 2013)
This article examines Pierre Elliott Trudeau's relationship with labour and social democratic organizations, 1949-1959. Using historiographic works, reflections from contemporary historical figures, and Trudeau's archival fonds, this essay demonstrates that his connections to labour and the left were motivated by his desire to enrich liberal democracy in both Quebec and Canada. Supporting labour unions and the provincial/federal Cooperative Commonwealth Federation during the early 1950s was imperative, as labour was a force for change and democratic renewal, and the CCF was the party with the strongest commitment to popular democracy, especially when contrasted with a Liberal Party and Union Nationale, which were dominated by regressive and financial interests. Using various theoretical approaches, including Ian McKay's Liberal Order Framework and Antonio Gramsci's concept of "trasformismo," I seek to show how Trudeau's leftist forays were informed by the desire to transform liberalism and capitalism in such a way that maintained their essences while inoculating them from their core flaws. This process of liberal transformation and hegemony is further emphasized in the later stages of the 1950s, as Trudeau began to reject social democratic and labour parties, arguing that they put their goals aside and join forces with liberals to fight for democracy first.
Keywords: Antonio Gramsci; Capitalism; Cooperative Commonwealth Federation; DEMOCRACY -- Canada; LABOR unions -- Canada -- History; Liberal Order Framework; Liberalism; Pierre Elliott Trudeau; Quebec labour; SOCIAL democracy; TRUDEAU, Pierre Elliott, 1919-2000; ordre libéral; syndicalisme québécois

The Limits of Voice: Are Workers Afraid to Express Their Health and Safety Rights? - Lewchuk, Wayne (Osgoode Hall Law Journal, 2013)
This article reconsiders the shift in Canada from an exclusively government-regulated occupational health and safety system to the Internal Responsibility System (IRS). The IRS gives workers rights, or “voice,” to manage, know about, and refuse unsafe working conditions. I present new evidence that worker voice and the IRS have weakened with the decline of unions and the rise of precarious employment. Survey data are analyzed from Ontario workers who rated the likelihood that raising a health and safety concern with their current employer would negatively affect their future employment. My analysis models how workers’ sex, race, unionization, sector, and degree of employment precarity affect their probability of exercising voice. Results of a logistic regression suggest the most precariously employed are the least likely to use voice. Consequently, I argue that the IRS should be supplemented with more external oversight in sectors where employment is most insecure.
Keywords: Industrial hygiene; Internal Responsibility system; Ministry of Labour; Ontario

Problematizing Labour's Agency: Rescaling Collective Bargaining in British Columbia Pulp and Paper Mills - Sweeney, Brendan; Holmes, John (Antipode, 2013)
This paper focuses on the contradictory nature and sometimes unintended consequences of workers' efforts to defend particular communities against the ravages of capital restructuring. In the past decade, pattern collective bargaining in the highly unionized British Columbia pulp and paper industry has faced enormous strains due to intense industry restructuring. Our analysis focuses on the repercussions of actions taken by union locals in two British Columbia towns-Port Alice and Port Alberni-to try to secure the survival of their pulp and paper mills and, even in the case of Port Alice, the continued existence of the community. Our analysis resonates with recent debates surrounding worker agency as well as writing in the 1980s which addressed the often contradictory and problematic nature of workers' struggles to 'defend place'; writing largely neglected in more recent work in labour geography.
Keywords: British Columbia; CORPORATE reorganizations -- Canada; Canada; Collective bargaining; LABOR unions -- Canada; Labour geography; PAPER industry -- British Columbia; PORT Alberni (B.C.); PORT Alice (B.C.); pulp and paper; scale

Abstracts, Volume 71 (Spring/Printemps 2013) (Labour / Le Travail, 2013)
English/French abstracts of articles in the Spring 2013 issue.

Abstracts, Volume 72 (Fall/Automne 2013) (Labour/Le Travail, 2013)
English/French abstracts of articles in the Fall 2013 issue.

Index — Volume 68 — 2013 (Relations industrielles / Industrial Relations, 2013)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Liste des appréciateurs – 2013 – List of Referees (Relations industrielles / Industrial Relations, 2013)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La vie professionnelle : âge, expérience et santé à l'épreuve des conditions de travail - Abouaissa, Siham (Relations industrielles / Industrial Relations, 2013)
La vie professionnelle : âge, expérience et santé à l’épreuve des conditions de travail, edited by Anne-Françoise Molinié, Corinne Gaudart and Valérie Pueyo, is reviewed.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

From Braceros to Pineros: Labour, Migration, and Changing Geographic and Social Landscapes in the United States - Acosta, Aidé (Labour / Le Travail, 2013)
The article reviews and comments on the books "They Saved the Crops: Labor, Landscape, and the Struggle Over Industrial Farming in Bracero-Era California," by Don Mitchell, "Braceros: Migrant Citizens and Transnational Subjects in the Postwar United States and Mexico," by Deborah Cohen, and "Pineros: Latino Labour and the Changing Face of Forestry in the Pacific Northwest," by Brinda Sarathy.
Keywords: BRACEROS: Migrant Citizens & Transnational Subjects in the Postwar United States & Mexico (Book); COHEN, Deborah; MITCHELL, Don; Nonfiction; PINEROS: Latino Labour & the Changing Face of Forestry in the Pacific Northwest (Book); SARATHY, Brinda; THEY Saved the Crops: Labor, Landscape & the Struggle Over Industrial Farming in Bracero-Era California (Book)

L’action syndicale à l’international vue du Sud : du global au local ou du local au global? - Adanhounme, Armel; Lévesque, Christian (Relations industrielles / Industrial Relations, 2013)
Ce texte propose une relecture du débat sur l’action syndicale à l’international entre la construction de coalitions globales et le développement de réseaux locaux. Il se base sur le récit des représentants syndicaux du secteur minier au Ghana et au Mexique. Les stratégies syndicales sont saisies sous les trois dimensions analytiques que sont les espaces de l’action syndicale à l’international, les modes d’interaction et le cadre de référence. L’objectif de l’article vise à comprendre comment les syndicats nationaux naviguent entre le local et le global, et les facteurs qui les poussent et les attirent vers les espaces transnationaux.Alors que les deux syndicats sont engagés dans un processus de renouvellement de leur action, leur stratégie transnationale diffère : les Ghanéens sont engagés dans le développement de nouvelles aptitudes et de nouveaux savoir-faire et les Mexicains dans la construction des coalitions. Ces constats suggèrent que l’action syndicale à l’international est fonction des contingences nationales. Primo, le syndicat ghanéen intervient surtout au niveau continental africain et privilégie le développement des compétences locales et nationales. De son côté, le syndicat mexicain est présent aussi bien au niveau continental nord-américain que transnational, notamment dans des campagnes de solidarité. Secundo, les Ghanéens entretiennent de faibles liens avec les autres syndicats. De l’autre, les Mexicains sont engagés dans un large répertoire d’action avec les syndicats nord-américains et les fédérations internationales. Tertio, les Ghanéens conçoivent leurs intérêts sur la base d’une forte identité clanique et définissent leur engagement international en termes de ressources. Pour leur part, les Mexicains bâtissent des coalitions transnationales sur la base d’une identité de classe.Allant au-delà de la dichotomie entre le local et le global, les stratégies syndicales à l’international sont socialement construites et localement enracinées. Elles s’expliquent par la dynamique de l’économie politique dans laquelle se trouvent insérés ces syndicats et les structures d’opportunité transnationale à leur portée.
Keywords: Ghana; Mexico; Mexique; México; coaliciones; coalitions; networks; redes; réseaux; sindicatos; syndicats; trade unions

Age Is Different: Revisiting the Contemporary Understanding of Age Discrimination in the Employment Setting - Alon-Shenker, Pnina (Canadian Labour and Employment Law Journal, 2013)
The author argues that the current test for age discrimination in Canada, which is based on the Supreme Court of Canada's decision in R. v. Kapp and which requires that discrimination be motivated by or perpetuate stereotyping or prejudice, has led adjudicators to fail to come to grips with wrongful ageism in the workplace. The fact that everyone ages, and that distinctions based on age may in the past have benefitted the same people who are now harmed by those distinctions, has in the author's view been given too much weight, thereby making discrimination against senior workers too easy to justify. She proposes that the legal test for age discrimination should focus on wrongs done in the present, and should not take account of any past or future benefits which may be attributed to a distinction drawn on the basis of age. On the basis of what the author calls the Dignified Lives Approach, she argues that an age-based distinc- tion should be held to be discriminatory if it violates any of these five principles: people of all ages must be assessed on their merits, must be treated as equals, must have enough means to live lives of dignity, must be socially included, and must retain their autonomy. Using as examples four recent cases of alleged age-based discrimination in the employment context decided by Canadian courts and administrative tribunals, the author demonstrates how the Dignified Lives Approach would in her view be more sensitive to different types of age dis- crimination and would bring more just outcomes.

Age, Gender, and Work: Small Information Technology Firms in the New Economy - Anderson, Jennifer (Labour / Le Travail, 2013)
The article reviews the book, "Age, Gender, and Work: Small Information Technology Firms in the New Economy," edited by Julie Anne McMullin.
Keywords: AGE, Gender & Work: Small Information Technology Firms in the New Economy (Book); EQUALITY in the workplace; INFORMATION technology industry; MCMULLIN, Julie Ann; Nonfiction

Partir pour la famille. Fécondité, grossesse et accouchement au Québec, 1900-1950. (French) - Baillargeon, Denyse (Labour / Le Travail, 2013)
The article reviews the book, "Partir pour la famille. Fécondité, grossesse et accouchement au Québec, 1900-1950," by Suzanne Marchand.
Keywords: Canada; FAMILIES; History; MARCHAND, Suzanne; Nonfiction; PARTIR pour la famille: Fecondite, grossesse et accouchement au Quebec 1900-1950 (Book)

The Disability Accommodation Gap in Canadian Workplaces: What Does It Mean for Law, Policy, and an Aging Population - Banks, Kevin; Chaykowski, Richard P.; Slotsve, George A. (Canadian Labour and Employment Law Journal, 2013)
The "accommodation gap" refers to the shortfall between those accom- modations which persons with disabilities require in order to work, and those workplace accommodations which they actually receive. This paper argues that the accommodation gap raises important issues for policy-makers in Canada, given the growing participation of older workers in the labour market and the fact that the incidence of disability increases with age. Such issues include the loss of productivity, higher poverty rates, increased cost of social programs, and failure to achieve the goals of human rights legislation. Using the results of an extensive analysis of data obtained from Statistics Canada's 2006 Participation and Activity Limitation Survey, the authors inquire into three questions: (1) Is there a workplace accommodation gap in Canada, and if there is, how big is it and whom does it affect? (2) Is it associated with age or aging, and there- fore likely to be aggravated by the aging of the Canadian population? (3) Are its causes likely to elude complaint-driven enforcement of human rights law because they are systemic? In answering these questions, the studyfinds that a large number of Canadians (about 35%) do not receive accommodations they need to work productively, or at all. Furthermore, the results show that the older the worker and the more severe his or her disability, the greater the accommo- dation gap. The authors suggest that thisfinding supports the view that employ- ers' decisions on whether to provide accommodation are influenced by economic considerations, stereotypes about the link between age and disability, the fact that certain types of accommodation may conflict with workplace culture, and other factors. Finally, the paper contends that the enforcement mechanism cur- rently in place is probably inadequate to deal with the accommodation gap, in view of the systemic nature of many of its causes. The authors set out a number of alternative options which may be more effective in closing the accommodation gap, and propose that those options be considered as part of a comprehensive policy review.

Bilan relatif aux dispositions de la LSST : vers une application intégrale? - Baril-Gingras, Geneviève; Vézina, Michel; Lippel, Katherine (Relations industrielles / Industrial Relations, 2013)
Dans un contexte où la qualité de vie au travail, le bien-être et la santé psychologique des employés sont actuellement au coeur des préoccupations des gestionnaires et des milieux de travail, les enjeux de santé organisationnelle deviennent incontournables. Or, malgré l’intérêt grandissant des chercheurs et des praticiens, la notion de santé organisationnelle a été l’objet de diverses conceptualisations et représente encore aujourd’hui un objet d’étude en pleine évolution. Dans cet ordre d’idées, cet article propose de faire une synthèse des approches contemporaines de la santé organisationnelle et d’investiguer comment cette thématique est abordée par les chercheurs québécois. Pour ce faire, une recension des écrits a d’abord été effectuée afin d’établir un portrait des connaissances acquises à ce jour. Ensuite, une enquête consultative a été réalisée auprès d’experts scientifiques québécois. À la fois les écrits et les experts consultés rapportent que la santé organisationnelle est un concept qui prend plusieurs sens, qui nécessite l’adoption d’une perspective plus globale et qui s’élargit à d’autres sphères que le travail. Or, contrairement à la documentation, les experts abordent surtout les aspects de la santé psychologique et moins la santé physique, et ils considèrent essentiellement les facteurs organisationnels comme des préoccupations de recherche future dans le domaine. Les résultats obtenus permettent de dresser un état des connaissances sur le concept de santé organisationnelle et son évolution, tout en identifiant les tendances émergentes susceptibles d’influencer les orientations scientifiques futures pour le regroupement stratégique en santé psychologique au travail du Réseau de recherche en santé et sécurité du travail du Québec. // More than thirty years after the adoption of the Quebec Act respecting occupational health and safety (AROHS), the regulations respecting the prevention programme (PP), the health programme specific to the establishment, joint OHS committees (JOHSC) and workers' safety representatives (WSR) have not yet been implemented in all occupational sectors, as was the original intention. The AROHS contains provisions respecting JOHSC's and WSR's on construction sites that are still not in force. In the vast majority of Canadian jurisdictions, measures such as the PP, the JOHSC and the WSR (in small workplaces) are mandatory in all economic sectors. The fact that these provisions at the heart of the AROHS do not cover all economic activity sectors cannot be justified based on scientific knowledge and on their application in other jurisdictions. Their adoption could, in the future, serve as the foundation for other measures that are required to respond to the changes in employment relations and the nature of work.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Federal legislation; Labor Unions; Prevention programs; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; enforcement; occupational health

Incidence Of Work And Workplace Injury Among Alberta Teens - Barnetson, Bob (Just Labour: A Canadian Journal of Work and Society, 2013)
Utilizing a convenience sample of nearly 2000 respondents drawn from administrative data, this study finds 43.7 percent of adolescents (aged 12-14) and 61.5 percent of young persons (aged 15-17) in the Canadian province of Alberta reported employment in 2011/12. Of those employed, 49.7 percent of adolescents and 59.0 percent of young persons reported at least one work-related injury in the previous year. This study also identifies widespread non-reporting of workplace injuries and seemingly ineffective hazard identification and safety training. These results add to the growing evidence that the regulation of teenage employment in Alberta fails to adequately protect these workers from injury.

Still Dying for a Living: Corporate Criminal Liability After the Westray Mine Disaster - Barnetson, Bob (Labour / Le Travail, 2013)
The article reviews the book, "Still Dying for a Living: Corporate Criminal Liability After the Westray Mine Disaster," by Steven Bittle.
Keywords: BITTLE, Steven; MINE accidents; Nonfiction; STILL Dying for a Living: Corporate Criminal Liability After the Westray Mine Disaster (Book)

American Labor, Congress, and the Welfare State, 1935-2010 - Battista, Andrew (Labour / Le Travail, 2013)
The article reviews the book, "American Labor, Congress, and the Welfare State, 1935-2010," by Tracy Roof.
Keywords: AMERICAN Labor, Congress & the Welfare State 1935-2010 (Book); History; Labor; Nonfiction; ROOF, Tracy; United States; WELFARE state

Spittoon Philosophers or Radical Revolutionaries? The Canadian Administration of the Industrial Workers of the World, 1932-35 - Beaulieu, Michel (Ontario History, 2013)
Historians contend that the heyday of the Industrial Workers of the World (IWW or Wobblies) in the U.S. and Canada ended when it was suppressed by the authorities in the First World War because of the “foreigners” within its ranks. However, the IWW went underground and re-emerged briefly in the late 1920s and 1930s as a force in lumber and mining unions in both countries. Little is known about its organization during this period, particularly the operations of the Canadian Administration established in 1932. This article explores the activities of Canadian Wobblies and their attempts to form a Canadian Administration between 1931 and 1935 in Port Arthur, Ontario. It establishes that the Canadian leadership increasingly separated itself from an ineffectual American leadership and attempted to establish uniquely “Canadian” polices.

L'activité des clients : un travail ? - Bellemare, Guy (Relations industrielles / Industrial Relations, 2013)
The article reviews the book, "L’activité des clients : un travail ?," edited by Sophie Bernard, Marie-Anne Dujarier and Guillaume Salariale.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Fragiles compétences - Bernier, Amélie (Relations industrielles / Industrial Relations, 2013)
The article reviews the book, "Fragiles compétences," edited by Sophie Bretesché and Cathy Krohmer.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Good Lands: A Meditation and History on the Great Plains - Berry, Susan (Labour / Le Travail, 2013)
The article reviews the book, "Good Lands: A Meditation and History on the Great Plains," by Frances W. Kaye.
Keywords: GOOD Lands: A Meditation & History on the Great Plains (Book); GREAT Plains; KAYE, Frances W.; Nonfiction

Gouverner les fins de carrière à distance. Outplacement et vieillissement actif en emploi - Bettache, Mustapha (Relations industrielles / Industrial Relations, 2013)
The article reviews the book, "Gouverner les fins de carrière à distance. Outplacement et vieillissement actif en emploi," by Thibauld Moulaert.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Up Against the Wall: The Political Economy Of the New Attack on the Canadian Labour Movement: A Reply to Andrew Jackson - Bhullar, Maya (Just Labour: A Canadian Journal of Work and Society, 2013)

Lire Industrial Relations Systems de John T. Dunlop. Les règles au coeur des relations de travail - Bilodeau, Pier-Luc (Relations industrielles / Industrial Relations, 2013)
The article reviews the book, "Gouverner les fins de carrière à distance. Outplacement et vieillissement actif en emploi," by Thibauld Moulaert.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Lessons for Litigators from ONA [Ontario Nurses' Associatiion] v. Chatham-Kent: A Union Perspective - Bisnar, Danielle; McIntyre, Elizabeth (Canadian Labour and Employment Law Journal, 2013)
Despite the abolition of mandatory retirement in most Canadian jurisdic- tions, statutory provisions generally still permit the denial of employment-re- lated benefits to workers aged 65 or over, or allow such benefits to be provided at a lower level than for workers under age 65. In ONA v. Chatham-Kent, an Ontario arbitrator upheld the constitutionality of provisions in that province's Human Rights Code and Employment Standards Act excluding workers over 65 from protection against age discrimination in the area of employment benefits, holding that while the impugned provisions infringed the equality rights set out in section 15 of the Charter of Rights and Freedoms, they were nonetheless justified under section 1 as a reasonable limit on those rights. Writing from the perspective of advocates for unions and employees, the authors review the development of the case law on mandatory retirement, drawing particular atten- tion to the "long shadow" cast by the Supreme Court of Canada's 1990 decision in McKinney. They go on to identify what they see as the flaws in the legal rea- soning of the award in Chatham-Kent, especially the arbitrator's acceptance of the notion (inherited in large part from the McKinney decision) that age is "dif- ferent" from other types of prohibited discrimination and his failure to closely scrutinize the legislature's policy choices with respect to employment benefits for older workers. Lastly, the authors extrapolate a number of lessons that may assist litigators in future challenges to statutory provisions that discriminate on the basis of age, notably the importance of framing section 15 claims by reference to intersecting grounds of discrimination (such as age and gender or disability) and of advocating for a lower level of deference to the legislature.

Black Internationalist Feminism: Women Writers of the Black Left, 1945-1995 - Boyce-Davies, Carole (Labour / Le Travail, 2013)
The article reviews the book, "Black Internationalist Feminism: Women Writers of the Black Left, 1945-1995," by Cheryl Higashida.
Keywords: BLACK Internationalist Feminism: Women Writers of the Black Left 1945-1995 (Book); BLACK feminism; BLACK women authors; HIGASHIDA, Cheryl; Nonfiction

"The common people have spoken with a mighty voice": Regina's Labour City Councils, 1936-1939 - Brennan, J. William (Labour / Le Travail, 2013)
Working-class poliltical activity at the municipal level in Regina began in 1914 on the initiative of members of the Regina Trades and Labour Council. Early on trade unionists reached out to the city's middle class, and together they founded a succession of Labour political parties in the 1920s. After 1930 members of the Canadian Brotherhood of Railway Employees also became involved. Success came in 1935, when the Civic Labour League, an informal alliance of social democrats and communists, won the mayoralty and a majority of the aldermanic seats on city council. Labour maintained its hold over City Hall until the end of the decade, but it did not accomplish much. It could not convince the province's Liberal government to take over full responsibility for the cost of relief or enact a special city charter that would give Regina wider powers (to construct social housing for example) and new sources of revenue. Then in 1939 Labour's political fortunes shifted dramatically. Accusations of communist influence in the selection of the Labour slate played into the hands of the city's business community, Regina's daily newspapers, and the Civic Voters' Association, which was founded on the eve of the civic election, and Labour suffered a crushing defeat.
Keywords: CENTRAL labor councils; CIVIC associations; Canada; History; Labor Unions; Labor movement; MUNICIPAL government; Middle class; REGINA (Sask.); WORKING class -- Political activity

Nurse Militancy and Strike Action - Briskin, Linda (Workers of the World: International Journal on Strikes, 2013)
Drawing on nurses strikes in many countries [including Canada], this article situates nurse militancy within the context of health care restructuring and neo-liberalism, the gendered construction of nursing work, the feminization of union density and of strikes, and gendered militancy. It explores the emergence of a militant discourse among nurses focussed on the public interest, what I call the politicisation of caring, which has supported a new approach to the ethics of striking. --Author's introduction

The Impact of Minimum Wages on Labour Market Transitions - Brochu, Pierre; Green, David A. (The Economic Journal, 2013)
We investigate differences in labour market transition rates between high and low minimum wage regimes using Canadian data spanning 1979–2008. We find that higher minimum wages result in lower hiring rates but also lower job separation rates. Importantly, the reduced separation rates are due mainly to reductions in layoffs, occur in the first six months of a job and are present for unskilled workers of all ages. Thus, jobs in higher minimum wage regimes are more stable but harder to get. For older workers, these effects are almost exactly offsetting, resulting in little impact on the employment rate.

Reshaping Expectations and Emerging Anxieties: Ideal Womanhood Receives a Makeover in Twentieth Century America - Brookfield, Tarah (Labour / Le Travail, 2013)
The article reviews and comments on "Creating Consumers: Home Economists in Twentieth-Century America" by Carolyn M. Goldstein, "Mom: The Transformation of Motherhood in Modern America" by Rebecca Jo Plant, and "Making Marriage Work: A History of Marriage and Divorce in the Twentieth-Century United States" by Kristin Celello.
Keywords: CELELLO, Kristin; CREATING Consumers: Home Economists in 20th-Century America (Book); GOLDSTEIN, Carolyn M.; MAKING Marriage Work: A History of Marriage & Divorce in the 20th-Century United States (Book); MOM: The Transformation of Motherhood in Modern America (Book); Nonfiction; PLANT, Rebecca Jo

Warrior Nation: Rebranding Canada in an Age of Anxiety - Brushett, Kevin (Labour / Le Travail, 2013)
The article reviews the book, "Warrior Nation: Rebranding Canada in an Age of Anxiety," by Ian McKay and Jamie Swift.
Keywords: MCKAY, Ian; NATIONAL characteristics, Canadian; Nonfiction; SWIFT, Jamie; WARRIOR Nation: Rebranding Canada in an Age of Anxiety (Book)

Is Industrial Unrest Reviving in Canada? Strike Duration in the Early Twenty-First Century: Is Industrial Unrest Reviving in Canada? - Brym, Robert; Bauer, Louise Birdsell; McIvor, Mitch (Canadian Review of Sociology/Revue canadienne de sociologie, 2013)
Canadian data on strike frequency, duration, and volume imply that the strike is withering away. Some research also suggests that strike duration is countercyclical. However, the early twenty‐first century was anomalous from the viewpoint of these expectations. After 2001, mean strike duration increased and was not countercyclical. This paper explains the anomaly by arguing that employers are seeking to scale back the wage gains of previous decades in the face of mounting public debt and the whip of an increasingly unfettered market. These conditions apparently motivate some workers to endure protracted work stoppages, irrespective of the phase of the business cycle, in an effort to protect their rights.

Workplace Voice and Civic Engagement: What Theory and Data Tell Us About Unions and Their Relationship to the Democratic Process - Bryson, Alex; Gomez, Rafael; Kretschmer, Tobias; Willman, Paul (Osgoode Hall Law Journal, 2013)
We offer an explanation for the phenomenon of declining democratic engagement by assuming that what happens at work is the primary driver of what occurs outside of the workplace. If workers are exposed to the formalities of collective bargaining and union representation, they also perhaps increase their attachment to, and willingness to participate in, structures of democratic governance outside of the workplace as well. In order for this argument to hold, one first needs to test whether individual union members are more prone to vote and participate in civil society than non-members: other research refers to this as the union voting premium. We find that the voice effect of unionism on democratic participation is significant and is larger for groups that are significantly under-represented when it comes to voting, namely those with fewer years of education, immigrants, and younger workers. We also discuss the legal implications of these findings.

Wife to Widow: Lives, Laws, and Politics in Nineteenth-Century Montreal - Buddle, Melanie (Labour / Le Travail, 2013)
The article reviews the book, "Wife to Widow: Lives, Laws, and Politics in Nineteenth-Century Montreal," by Bettina Bradbury.
Keywords: BRADBURY, Bettina; Canada; History; Marriage; Marriage law; Nonfiction; WIFE to Widow: Lives, Laws & Politics in 19th-Century Montreal (Book)

Intern Nation: How to Earn Nothing and Learn Little in the Brave New Economy - Burstein, Rachel (Labour / Le Travail, 2013)
The article reviews the book, "Intern Nation: How to Earn Nothing and Learn Little in the Brave New Economy," by Ross Perlin.
Keywords: INTERN Nation: How to Earn Nothing & Learn Little in the Brave New Economy (Book); INTERNSHIP programs; Nonfiction; PERLIN, Ross

Vineyards & Vaqueros: Indian Labor and the Economic Expansion of Southern California, 1771-1877 - Callahan, Manuel (Labour / Le Travail, 2013)
The article reviews the book, "Vineyards and Vaqueros: Indian Labor and the Economic Expansion of Southern California, 1771-1877," by George Harwood Phillips.
Keywords: CALIFORNIA Indians (North American people); Nonfiction; PHILLIPS, George Harwood; VINEYARDS & Vaqueros: Indian Labor & the Economic Expansion of Southern California 1771-1877 (Book)

Disintegrating Democracy at Work: Labor Unions and the Future of Good Jobs in the Service Economy - Campbell, Shelagh (Relations industrielles / Industrial Relations, 2013)
Disintegrating Democracy at Work: Labor Unions and the Future of Good Jobs in the Service Economy, by Virginia Doellgast, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Call centers; Democracy; Labor Unions; Roles; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Globalization and Precarious Forms of Production and Employment: Challenges for Workers and Unions - Cantin, Étienne (Relations industrielles / Industrial Relations, 2013)
Globalization and Precarious Forms of Production and Employment: Challenges for Workers and Unions, edited by Carole Thornley, Steve Jefferys and Beatrice Appay, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Employment; Globalization; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Régimes collectifs de rémunération variable, justice organisationnelle et engagement - Caron, Isabelle; Ben Ayed, Ahmed; Vandenberghe, Christian (Relations industrielles / Industrial Relations, 2013)
Cette étude examine les relations entre les caractéristiques des régimes collectifs de rémunération variable à court terme (soit des régimes qui octroient une prime aux employés en fonction du rendement), la justice organisationnelle et l’engagement organisationnel. Son intérêt pratique repose sur l’idée que les régimes de rémunération variable sont instaurés pour fidéliser les employés. À partir d’une revue de la littérature, quatre caractéristiques des régimes collectifs de rémunération variable sont identifiées : 1) le lien d’instrumentalité perçu (perception d’un lien entre le rendement et la rémunération); 2) la prime versée (le montant versé à l’employé dans le cadre du régime); 3) l’intensité de la communication organisationnelle (les sources d’information mises à la disposition des employés); et 4) les communications du supérieur immédiat relativement au régime de rémunération. Notre hypothèse centrale est que ces caractéristiques sont liées à l’engagement affectif et de continuité des employés par l’entremise de quatre dimensions de justice organisationnelle, soit la justice distributive, la justice procédurale, la justice informationnelle et la justice interpersonnelle.À partir d’un échantillon de 313 répondants appartenant à trois ordres professionnels, des analyses d’équations structurelles révèlent que la justice procédurale médiatise la relation entre 1) l’intensité de la communication organisationnelle et la communication du supérieur et 2) l’engagement de continuité. De même, la justice informationnelle médiatise la relation entre 1) l’intensité de la communication organisationnelle et la communication du supérieur et 2) l’engagement affectif. Enfin, la justice interpersonnelle médiatise la relation entre la communication du supérieur et l’engagement de continuité. Cette étude montre que la communication par l’organisation et le supérieur immédiat quant aux règles régissant le fonctionnement des régimes collectifs de rémunération variable constituent la pierre angulaire de la perception de justice (procédurale, informationnelle et interpersonnelle) par les employés, ce qui indirectement stimule leur engagement affectif et de continuité.
Keywords: affective and continuance commitment; collective incentive plans; compromiso afectivo y de continuidad; distributive; engagement affectif et de continuité; informacional; informational and interpersonal justice; informationnelle; interpersonal; interpersonnelle; justice distributive; justicia distributiva; procedural; procédurale; remuneración variable; rémunération variable

Dis-identification in Organizations and Its Role in the Workplace - Chang, Kirk; Kuo, Chien-Chih; Su, Man; Taylor, Julie (Relations industrielles / Industrial Relations, 2013)
This research seeks to augment contemporary theories of employee dis-identification in organizations (DiO) and its importance in the workplace. An anonymous questionnaire survey was conducted, 304 employees were recruited across eight organizations in Taiwan (with anti-CMV strategies adopted). Distinct from previous studies, this research stated that organizational identification and dis-identification were neither heterogeneous nor independent constructs. Statistical evidence supported this statement and explained that organizational identification and dis-identification were inter-related constructs. Specifically, two DiO antecedents were revealed, including: person-organization fit and abusive supervision. Unlike previous studies, DiO was not correlated with poor employee performance; rather, it was correlated with workplace deviance, intention to quit the job, and voice-extra-role-behaviours. Theoretical and managerial implications are discussed.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Discriminant analysis; Labor Unions; Organizational behavior; Regression analysis; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

Romancing the Revolution: The Myth of Soviet Democracy and the British Left - Chapman, Roger (Labour / Le Travail, 2013)
The article reviews the book, "Romancing the Revolution: The Myth of Soviet Democracy and the British Left," by Ian Bullock.
Keywords: BULLOCK, Ian; GREAT Britain -- Foreign relations -- Soviet Union; Nonfiction; ROMANCING the Revolution: The Myth of Soviet Democracy & the British Left (Book)

Defending Age Distinctions in Employee Benefits after the Elimination of Mandatory Retirement - Charney, Robert E.; Horner, Matthew (Canadian Labour and Employment Law Journal, 2013)
Approaching the issue through their review of several recent court and tribunal decisions, the authors argue that the legislative policy choice in Ontario and other jurisdictions to permit age-based distinctions in the provision of benefits to employees over age 65, notwithstanding the abolition of mandatory retirement, was not only reasonable but necessary. That choice, in their view, represents a fair, and amply justified, balance between the right of individual employees to continue working past 65, and the right of employees as a collec- tivity to freely negotiate benefit provisions and group insurance plans that are in the interests of the group as a whole.

Principles for Labour Relations Policy Reform in the Wake of the Drummond Report on Ontario's Public Services Prospects for Reform of Industrial Relations in the Ontario Broader Public Sector: Papers from the Workshop on the Drummond Report Centre for Law in the Contemporary Workplace, Queen's University, June 22, 2012 - Chaykowski, Richard P.; Hickey, Robert S. (Canadian Labour and Employment Law Journal, 2013)
The provincial broader public sector (BPS) in Ontario com- prises the full range of government services and Crown corporations, as well as health care and education. The BPS is vital to the Ontario economy as well as to the citizens who use its services; it accounts for about half of the province's gross domestic product. Each of its com- ponent parts depends on direct government funding or government transfers, or is at least regulated by the government. The 2008 global financial crisis and its impact on the management of Ontario's public services has brought industrial relations practices and outcomes in the BPS into sharp focus. In 2011, the Ontario government established the Commission on the Reform of Ontario's Public Services, chaired by Don Drummond (the Drummond Commission),' with a view to enhancing the efficiency of BPS services.

Les comportements de citoyenneté du personnel soignant : lorsque le sens et la confiance deviennent incontournables - Chênevert, Denis; Jourdain, Geneviève; Tremblay, Marie-Claude (Relations industrielles / Industrial Relations, 2013)
La crise des finances publiques et l’accroissement de la demande en soins de santé amènent de plus en plus d’hôpitaux à implanter des pratiques de gestion à haute implication (PGHI). Or, les études sur le lien entre ces pratiques et la performance organisationnelle se font plutôt rares dans le secteur hospitalier. De plus, les recherches se sont surtout limitées à montrer l’existence d’un lien direct entre les PGHI et la performance organisationnelle, donnant ainsi peu d’information sur le processus qui mène à cette performance. Cette étude vise à combler ces lacunes en examinant le rôle médiateur joué par l’habilitation psychologique (HP) dans la relation entre les PGHI et les comportements de citoyenneté organisationnelle (CCO) du personnel soignant, un déterminant important de la qualité des soins de santé. De plus, puisqu’une relation de collaboration avec les médecins, basée sur la confiance, serait au coeur du sentiment de pouvoir du personnel soignant, l’effet modérateur de la confiance envers les médecins sur la relation entre les PGHI et l’HP est aussi examiné. Ainsi, l’étude valide un modèle spécifiant des relations différenciées entre les PGHI (autonomie, développement des compétences, partage d’information, reconnaissance) et les cognitions de l’HP (compétences, autodétermination, sens, impact), celles-ci étant modérées par la confiance envers les médecins. Enfin, l’étude cherche à vérifier si les cognitions de l’HP qui inciteraient aux CCO interagissent entre elles selon une séquence prédéterminée. Basée sur un sondage réalisé auprès de 176 employés délivrant des soins de santé et leurs supérieurs immédiats, l’étude suggère que la relation entre certaines PGHI (autonomie et développement des compétences) et les CCO est tributaire du sens du travail et de la confiance envers les médecins. Aussi, les cognitions de l’HP seraient liées entre elles selon une séquence particulière conférant à l’autodétermination un rôle central dans cette séquence.
Keywords: autonomie; autonomy; autonomía; competence; competencia; comportamientos de ciudadanía organizacional; comportements de citoyenneté organisationnelle; compétence; confiance; confianza; habilitación sicológica; habilitation psychologique; healthcare sector; meaning; organizational citizenship behaviour; psychological empowerment; secteur de la santé; sector de la salud; sens du travail; sentido de trabajo; trust

Dear Canadian Labour Movement: A Reply To Andrew Jackson - Chong, Patricia (Just Labour: A Canadian Journal of Work and Society, 2013)

Labour Struggles for Workplace Justice: Migrant and Immigrant Worker Organizing in Canada - Choudry, Aziz; Thomas, Mark (Journal of Industrial Relations, 2013)
This article explores the dynamics of labour organizing among migrant and immigrant workers in Canada, focusing on two case studies: first, recent efforts to organize migrant farmworkers in the Seasonal Agricultural Workers’ Program; and, second, the work of the Immigrant Workers’ Centre in Montreal. The Seasonal Agricultural Workers’ Program, which employs workers from Mexico and Caribbean countries, is often viewed by policymakers and employers as an example of ‘best practices’ in migration policy. Yet workers in the program experience seasonal employment characterized by long hours and low wages, and are exempt from many basic labour standards. The Immigrant Workers’ Centre formed in 2000 to provide a safe place for migrant and racialized immigrant workers to come together around problems in their workplaces. Through these case studies, we examine labour organization efforts including advocacy and grassroots organizing through the Immigrant Workers’ Centre and legal challenges attempting to secure recognition of freedom of association rights for farmworkers. The article explores the ‘limits and possibilities’ of these strategies, and concludes by assessing the implications for labour organizing among the growing numbers of migrant and immigrant workers employed in a wide range of low-wage, low-security occupations due to the recent expansion of Canada’s Temporary Foreign Worker Program.
Keywords: Canada; labour organizing; migrant and immigrant workers; temporary foreign worker programs

Jobs and Justice: Fighting Discrimination in Wartime Canada, 1939-1945 - Clément, Dominique (Labour / Le Travail, 2013)
The article reviews the book, "Jobs and Justice: Fighting Discrimination in Wartime Canada, 1939-1945," by Carmela Patrias.
Keywords: Canada; History; JOBS & Justice: Fighting Discrimination in Wartime Canada 1939-1945 (Book); Nonfiction; PATRIAS, Carmela; RACE discrimination in employment; Race discrimination

Des conflits de rôle au stress perçu : Les managers ont-ils besoin d’être soutenus? - Codo, Sylvie; Soparnot, Richard (Relations industrielles / Industrial Relations, 2013)
De nombreuses recherches présentent le soutien social perçu comme un levier efficace de gestion du stress au travail. Notre recherche propose de vérifier cette hypothèse en interrogeant le rôle modérateur attribué au soutien social perçu provenant des supérieurs et des subordonnés dans les relations entre les conflits de rôle et le stress chez des managers intermédiaires (MI) et des managers de proximité (MP) du secteur public. Le modèle exigences-ressources professionnelles (Bakker et Demerouti, 2007) nous a servi de cadre théorique. D’après ce modèle, le soutien social perçu constitue une ressource professionnelle permettant d’atténuer les effets délétères des exigences professionnelles sur la santé mentale. Les données collectées auprès de 310 managers dans des administrations publiques locales confirment partiellement cette hypothèse. En effet, notre recherche ne permet pas d’appuyer dans un premier temps l’influence modératrice du soutien social perçu provenant des supérieurs et du soutien social perçu provenant des subordonnés dans la relation entre les conflits de rôle et le stress perçu chez les MI. Des résultats similaires sont observés dans certains cas chez des MP. Conséquemment, l’hypothèse de la non-mobilisation du soutien social comme une ressource professionnelle par les managers dans certaines conditions est avancée pour discuter ces résultats. Ces derniers révèlent dans un second temps que l’efficacité du soutien social perçu dépend de plusieurs facteurs : la nature et la source du soutien social perçu, le type de conflit de rôle en présence et le niveau hiérarchique des managers bénéficiaires (MI et MP). Ainsi, plus que MI, les MP semblent plus réceptifs au soutien social d’estime perçu provenant de leurs supérieurs lorsqu’ils sont confrontés aux conflits de rôle. Par conséquent, leur niveau de stress diminue. Afin de gérer le stress des MP occasionné par les conflits de rôle, nos implications managériales sont orientées vers une reconnaissance de leurs compétences professionnelles.
Keywords: administraciones públicas locales; administrations publiques locales; directivos de proximidad; directivos intermedios; job demands-resources model; local public administration; managers de proximité; managers intermédiaires; middle managers; modelo exigencias-recursos profesionales; modèle exigences-ressources professionnelles; proximity managers

Brève histoire des femmes au Québec - Cohen, Yolande (Labour / Le Travail, 2013)
The article reviews the book, "Brève histoire des femmes au Québec," by Denyse Baillargeon.
Keywords: BAILLARGEON, Denyse; BREVE histoire des femmes au Quebec (Book); Nonfiction; QUEBEC (Province); Women

Making Feminist Politics: Transnational Alliances Between Women and Labour - Conway, Janet (Labour / Le Travail, 2013)
The article reviews the book, "Making Feminist Politics: Transnational Alliances Between Women and Labour," by Suzanne Franzway and Mary Margaret Fonow.
Keywords: FONOW, Mary Margaret; FRANZWAY, Suzanne; History; MAKING Feminist Politics: Transnational Alliances Between Women & Labor (Book); Nonfiction; WOMEN in the labor movement; Women employees

Quebec Research on Work-related Musculoskeletal Disorders: Deeper Understanding for Better Prevention - Côté, Julie N.; Ngomo, Suzy; Stock, Susan; Messing, Karen; Vézina, Nicole; Antle, David; Delisle, Alain; Bellemare, Marie; Laberge, Marie; St-Vincent, Marie (Relations industrielles / Industrial Relations, 2013)
Work-related musculoskeletal disorders (WMSDs) represent a complex and multi-faceted challenge, requiring multi-disciplinary, multi-perspective research approaches ranging from fundamental, basic science research to studies of applied workplace-based interventions. Members of the MSD Research Axis of the Quebec Occupational Health and Safety Research Network have been actively engaged in WMSD research across this full spectrum, contributing to significant knowledge advances on WMSD. Despite this, many facets of WMSDs remain insufficiently understood, and WMSDs remain a considerable problem for our society. Advances on interventions to decrease risk and improve workers' health are notable, although the level and quality of evidence about the effectiveness of ergonomic interventions must be improved. This paper highlights contributions of the group towards the advancement of understanding and prevention of WMSDs.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Disease prevention; Labor Unions; Musculoskeletal diseases; Research & development--R&D; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; occupational health

Raising Retail: Organizing Retail Workers in Canada and the United States - Coulter, Kendra (Labor Studies Journal, 2013)
Retail workers are a significant but largely unorganized group in Canada and the United States. However, in recent years, there has been a marked increase in efforts to organize retail workers, including pursuit of innovative structures and strategies. The author focuses on the dominant threads of contemporary retail organizing work in Canada and the United States, outlining three current organizing vehicles: unionization, store-based networks, and occupation or sector-based associations. The author then reflects on the strengths, weaknesses, and possibilities of these approaches, independently and collectively, and emphasizes the need to confront the social and cultural as well as the economic devaluation of retail workers.

L'élaboration du droit de l'emploi au Québec : ses sources législatives et judiciaires - Coutu, Michel (Relations industrielles / Industrial Relations, 2013)
L’élaboration du droit de l’emploi au Québec : ses sources législatives et judiciaires, by Fernand Morin, is reviewed.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Santé organisationnelle : Où en sommes-nous et vers où allons-nous au Québec? - Dagenais-Desmarais, Véronique; Dufour, Marie-Ève; St-Hilaire, France; Hébert, Rachèle (Relations industrielles / Industrial Relations, 2013)
Dans un contexte où la qualité de vie au travail, le bien-être et la santé psychologique des employés sont actuellement au coeur des préoccupations des gestionnaires et des milieux de travail, les enjeux de santé organisationnelle deviennent incontournables. Or, malgré l’intérêt grandissant des chercheurs et des praticiens, la notion de santé organisationnelle a été l’objet de diverses conceptualisations et représente encore aujourd’hui un objet d’étude en pleine évolution. Dans cet ordre d’idées, cet article propose de faire une synthèse des approches contemporaines de la santé organisationnelle et d’investiguer comment cette thématique est abordée par les chercheurs québécois. Pour ce faire, une recension des écrits a d’abord été effectuée afin d’établir un portrait des connaissances acquises à ce jour. Ensuite, une enquête consultative a été réalisée auprès d’experts scientifiques québécois. À la fois les écrits et les experts consultés rapportent que la santé organisationnelle est un concept qui prend plusieurs sens, qui nécessite l’adoption d’une perspective plus globale et qui s’élargit à d’autres sphères que le travail. Or, contrairement à la documentation, les experts abordent surtout les aspects de la santé psychologique et moins la santé physique, et ils considèrent essentiellement les facteurs organisationnels comme des préoccupations de recherche future dans le domaine. Les résultats obtenus permettent de dresser un état des connaissances sur le concept de santé organisationnelle et son évolution, tout en identifiant les tendances émergentes susceptibles d’influencer les orientations scientifiques futures pour le regroupement stratégique en santé psychologique au travail du Réseau de recherche en santé et sécurité du travail du Québec.
Keywords: Delphi method; health; litterature review; méthode Delphi; método Delphi; organisation; organización; organization; recension des écrits; recensión bibliográfica; salud; santé; trabajo; travail; work

Care, Paid Work, and Work-Family-State Nexus: Learning from the US - Daly, Mary (Labour / Le Travail, 2013)
The article reviews and comments on the books, "Caring For America: Home Health Workers in the Shadow of the Welfare State" by Eileen Boris and Jennifer Klein, "Forced to Care: Coercion and Caregiving in America" by Evelyn Nakano Glenn and "Reshaping the Work-Family Debate: Why Men and Class Matter" by Joan C. Williams.
Keywords: BORIS, Eileen; CARING for America: Home Health Workers in the Shadow of the Welfare State (Book); FORCED to Care: Coercion & Caregiving in America (Book); GLENN, Evelyn Nakano; KLEIN, Jennifer; Nonfiction; RESHAPING the Work-Family Debate: Why Men & Class Matter (Book); WILLIAMS, Joan, 1952-

L’organisation des petits vendeurs de journaux à Montréal, 1903-1917 : comme quoi la jeunesse et la précarité ne sont pas des obstacles infranchissables à la syndicalisation - Dansereau, Bernard (Bulletin d'histoire politique, 2013)

(Se) Former pour transformer le travail : dynamiques de constructions d'une analyse critique du travail - David, Hélène (Relations industrielles / Industrial Relations, 2013)
The article reviews the book, "Gouverner les fins de carrière à distance. Outplacement et vieillissement actif en emploi," by Thibauld Moulaert.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Security of Retirement Benefits in Canada: You Bet Your Life - Davis, Ronald B. (Canadian Labour and Employment Law Journal, 2013)
This paper provides a careful review and analysis of employment-based pensions and other post-retirement benefits that may be available to Canadian workers when they retire, with particular emphasis on the extent to which such benefits are vulnerable to unilateral employer alteration or cancellation, or to the risks which arise in the event of the employer's insolvency. Taking stock of key differences between the rights of unionized employees and non-unionized ones, the author argues that the legal regimes governing common law employ- ment, collective bargaining and pensions offer varying degrees of security for post-retirement benefits, depending on the type of regime applicable to the work- place and the type of benefit. However, as the paper goes on to explain, the situ- ation changes dramatically if the employer becomes insolvent - all the more so because the federal legislation which regulates creditors' rights in an insolvency enjoys paramountcy over the provincial legislation that deals with employment, collective bargaining and pensions (including any provision made in that prov- incial legislation for so-called "deemed trusts"). The author sets out and weighs the numerous risks confronting employees' pension and post-retirement benefit entitlements in both an insolvency proceeding and in a restructuring, again drawing attention to the different dynamics that may come into play in unionized and non-unionized workplaces. In general, he finds, the security of pensions is stronger than that of non-pension benefits, but will still depend on the adequacy of the pension plan's funding before insolvency.

Le Réseau de recherche en santé et sécurité du travail du Québec : Un bilan de dix ans / The Quebec Occupational Health and Safety Research Network: A Ten Year Update - Desmarais, Lise; Legendre, Gabrielle (Relations industrielles / Industrial Relations, 2013)
Editorial introduction to the issue.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

The Quebec Occupational Health and Safety Research Network: A Ten Year Update - Desmarais, Lise; Legendre, Gabrielle (Relations industrielles / Industrial Relations, 2013)
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Nuancing Neoliberalism: Lessons Learned from a Failed Immigration Experiment - Dobrowolsky, Alexandra (Journal of International Migration and Integration, 2013)
This paper contributes to current debates around neoliberalism and subnational developments in Canadian immigration policy. In response to critiques of neoliberalism’s “promiscuity,” scalar and governmentality frameworks are used to analyze Nova Scotia’s failed economic nominee category experiment. The competing choices, calculations, and commitments at stake at “meso”- and “micro”-scales reveal a more complex and compelling reality that underscores the contributions and challenges of a range of political actors. This, in turn, suggests possible disruptions to neoliberalization and seeks to strike a better balance between structure and agency, as well as economic and social immigration priorities.
Keywords: Agency; Decentralization and devolution; Demography; Governmentality; Immigration policy Canada; Migration; Neoliberalism; Population Economics; Provincial nominee program Nova Scotia; Scalar analysis; Sociology, general

Offshore Petroleum Politics: Regulation and Risk in the Scotian Basin - Doern, Bruce (Labour / Le Travail, 2013)
The article reviews the book, "Offshore Petroleum Politics: Regulation and Risk in the Scotian Basin," by Peter Clancy.
Keywords: CLANCY, Peter; Nonfiction; Nova Scotia; OFFSHORE Petroleum Politics: Regulation & Risk in the Scotian Basin (Book); PETROLEUM in submerged lands

Advancement in Quebec Research on the Prevention of Risks Related to Occupational Exposure to Nanomaterials - Dolez, Patricia; Cloutier, Yves; Noël, Alexandra; Tabet, Lyes; Gautrin, Denyse; Debia, Maximilien; L'Espérance, Gilles; Hallé, Stéphane; Bahloul, Ali; Vinches, Ludwig (Relations industrielles / Industrial Relations, 2013)
The nanotechnology field is a growing industry, particularly in Quebec: occupational exposure risks already exist and should increase exponentially. In recent years, work has been undertaken in Quebec to develop knowledge for improving the prevention of nanomaterial-related risks. In particular, a group of researchers, professionals and students involved in the nanotechnology field was created in 2006 under the aegis of the Quebec Occupational Health and Safety Research Network. Its aim is to share the expertise of the different stakeholders in this field in order to promote multidisciplinary collaboration and more rapid advancement in research.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Health risk assessment; Labor Unions; Nanomaterials; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; occupational health

Emotionalizing Organizations and Organizing Emotions - Dompierre, Johanne (Relations industrielles / Industrial Relations, 2013)
The article reviews the book, "Emotionalizing Organizations and Organizing Emotions," edited by Barbara Sieben and Asa Wettergren.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Dwelling Places and Social Spaces: Revealing the Environments of Urban Workers in Victoria Using Historical GIS - Dunae, Patrick A.; Lafreniere, Donald J.; Gilliland, Jason A.; Lutz, John S. (Labour / Le Travail, 2013)
The Pacific Northwest underwent rapid economic growth in the late 19th century and cities on both sides of the Canada/US border burgeoned. The building boom was sustained by a large cohort of tradesmen and skilled labourers who lived in modest cabins, tenement blocks, boarding houses, and residential hotels. Most of these urban wageworkers were unmarried. They left few records of their experiences outside the job site or union hall. In this case study of Victoria, British Columbia circa 1891, we deployed a historical geographical information system (HGIS) to reconstitute the urban residential and social space of bout 2,000 otherwise elusive working men. Our research framework combines qualitative methods that are familiar to historians and quantitative methods favoured by geospatial researchers. By integrating both qualitative and quantitative data, we are able to represent the multiple spatial conditions experienced by Victoria's wageworkers in the early 1890s. In the process, we repopulated the city and reconstructed a largely vanished urban landscape. A primary objective of the essay is to demonstrate how GIS can be used as a research tool and new epistemology in the field of labour history.
Keywords: CITY dwellers; Geographic information systems; History; QUANTITATIVE research; Qualitative research; VICTORIA (B.C.); WORKING class -- History; WORKING class -- Housing

Winnipeg Beach: Leisure and Courtship in a Resort Town, 1900-1967 - Dunkin, Jessica (Labour / Le Travail, 2013)
The article reviews the book, "Winnipeg Beach: Leisure and Courtship in a Resort Town, 1900-1967," by Dale Barbour.
Keywords: BARBOUR, Dale; History; Nonfiction; RESORTS; WINNIPEG Beach: Leisure & Courtship in a Resort Town 1900-1967 (Book)

The Anthropological Study of Class and Class Consciousness - Field, Les W. (Labour / Le Travail, 2013)
The article reviews the book, "The Anthropological Study of Class and Class Consciousness," edited by E. Paul Durrenberger.
Keywords: ANTHROPOLOGICAL Study of Class & Class Consciousness, The (Book); Class consciousness; DURRENBERGER, E. Paul; Nonfiction

A Wilder West: Rodeo in Western Canada - Field, Russell (Labour / Le Travail, 2013)
The article reviews the book, "A Wilder West: Rodeo in Western Canada," by Mary-Ellen Kelm.
Keywords: History; KELM, Mary-Ellen; Nonfiction; Rodeos; WILDER West: Rodeo in Western Canada, A (Book)

No Man's Land: Jamaican Guestworkers in America and the Global History of Deportable Labor - Fink, Joey (Labour / Le Travail, 2013)
The article reviews the book, "No Man's Land: Jamaican Guestworkers in America and the Global History of Deportable Labor," by Cindy Hahamovitch.
Keywords: FOREIGN workers -- United States; HAHAMOVITCH, Cindy; History; NO Man's Land: Jamaican Guestworkers in America & the Global History of Deportable Labor (Book); Nonfiction

Le leadership transformationnel comme source d’engagement syndical : Le rôle modérateur de la justice - Fortin-Bergeron, Chloé; Doucet, Olivier; Hennebert, Marc-Antonin (Relations industrielles / Industrial Relations, 2013)
Si certains travaux sur le renouveau syndical reconnaissent l’importance de s’intéresser au fait représentatif et plus particulièrement à la relation représentant-représenté, les effets du leadership des représentants syndicaux sur leurs membres demeurent très peu étudiés. Pour pallier ce déficit analytique, cette étude analyse l’effet direct du leadership transformationnel du représentant syndical sur l’engagement syndical ainsi que l’effet modérateur de la justice distributive et procédurale du syndicat local sur cette relation. Des analyses de régressions linéaires multiples, menées auprès d’un échantillon de 834 travailleurs syndiqués d’une entreprise québécoise, soutiennent l’existence d’un lien positif entre le leadership transformationnel du représentant syndical et l’engagement envers le syndicat, et ce, après avoir contrôlé certaines caractéristiques des répondants dont l’âge, le sexe, l’ancienneté et le niveau de scolarité. En outre, nos résultats démontrent que la justice syndicale de type procédural modère cette relation. En ce sens, un syndicat local reconnu comme offrant des procédures justes et équitables viendrait rehausser les efforts de leadership de ses représentants.Sur le plan théorique, cette étude supporte la théorie des échanges sociaux ainsi que le modèle d’engagement au groupe, en démontrant notamment que la justice et le leadership transformationnel jouent sur des mécanismes affectifs similaires. Sur le plan pratique, les résultats soulignent l’importance, pour les syndicats locaux, de se pencher sur les pratiques et sur les modes de fonctionnement au niveau local qui sont susceptibles de favoriser la perception de justice procédurale. Ces constats ouvrent ainsi de nouvelles avenues de recherche relatives aux efforts de revitalisation des syndicats locaux et, plus spécifiquement, aux effets du leadership syndical et à la dynamique sous-jacente à la relation représentant-représenté.
Keywords: distributive justice; engagement syndical; group engagement model; implicación sindical; justice distributive; justice procédurale; justicia distributiva; justicia procedural; leadership; liderazgo; modelo de adhesión al grupo; modèle d’engagement au groupe; procedural justice; social exchange theory; teoría de intercambios sociales; théorie des échanges sociaux; union commitment

A Company of One: Insecurity, Independence and the New World of White-Collar Unemployment - Foster, Jason (Labour / Le Travail, 2013)
The article reviews the book, "A Company of One: Insecurity, Independence and the New World of White-Collar Unemployment," by Carrie M. Lane.
Keywords: COMPANY of One: Insecurity, Independence & the New World of White-Collar Unemployment, A (Book); Employment; FINANCIAL crises; LANE, Carrie M.; Nonfiction; United States; White collar workers

In the Shadows: Exploring the Notion of "Community" for Temporary Foreign Workers in a Boomtown - Foster, Jason; Taylor, Alison (Canadian Journal of Sociology, 2013)
The rapid expansion of the oil sands in northern Alberta in the early 21st century led to the use of significant numbers of temporary foreign workers. These foreign workers became a part of the region’s so-called “shadow population.” This paper examines how the presence of foreign workers affects conceptions of community and social cohesion through the experiences of foreign workers employed in oil sands construction. The study finds foreign workers are excluded from the life of the community due to their differential exclusion, vulnerable and precarious connection to the labour market, experiences of discrimination, and conflicted transnational community identities. The paper discusses the shortcomings of community and social cohesion approaches in addressing temporary foreign workers and considers the policy limitations of a widespread temporary foreign worker program.

Contribution à un modèle explicatif de la charge de travail : le cas du service à la clientèle - Fournier, Pierre-Sébastien; Montreuil, Sylvie; Villa, Julie (Relations industrielles / Industrial Relations, 2013)
La rapidité des changements qui s’opèrent dans les organisations engendre une intensification du travail qui se traduit par une augmentation de la charge de travail. La littérature scientifique identifie de plus en plus clairement la charge de travail comme un facteur de risques dont les répercussions affectent les individus et les organisations. Bien que les connaissances actuelles portant sur la charge de travail permettent de quantifier des conséquences humaines ou organisationnelles, elles sont difficiles à utiliser pour agir dans l’amélioration des situations de travail. Cet article a pour objectif de contribuer à la modélisation de la charge de travail dans sa globalité et sa complexité à l’intérieur de la dynamique de l’individu, de son activité professionnelle et de son contexte organisationnel. Elle vise à définir des composantes de la charge de travail et à cerner des facteurs qui l’influencent directement ou indirectement à partir de situations de travail réelles. Une recherche terrain s’est déroulée dans une organisation du secteur de l’assurance auprès de préposés au service à la clientèle en privilégiant des observations, des entretiens individuels et de groupe. Les activités réelles de travail des préposés ont été analysées en privilégiant le modèle de l’activité réelle de travail tel qu’utilisé en ergonomie. Cinq facteurs dynamiques de la charge de travail émergent de la recherche et ils permettent de réviser et d’enrichir un modèle explicatif de la charge de travail.
Keywords: approche ergonomique; carga de trabajo; charge de travail; customer service agents; daily working reality; empleados del servicio a la clientela; enfoque ergonómico; ergonomic approach; intensificación del trabajo; intensification du travail; préposés au service à la clientèle; trabajo real; travail réel; work intensification; workload

“Liking” Your Union: Unions and New Social Media during Election Campaigns - Fowler, Tim; Hagar, Doug (Labor Studies Journal, 2013)
The authors examine the use of new social media (NSM) by Canadian unions during electoral campaigns. The use of NSM by unions is emerging in Canada, and the authors study the 2011 federal and provincial elections, arguably the first time Canadian unions used NSM as part of their electoral strategies. The authors show that unions with close partisan ties to the New Democratic Party are more likely to embrace NSM as an electoral tactic than unions with no partisan ties or unions that engage in strategic voting.

Labour at the Lakehead: Ethnicity, Socialism, and Politics, 1900-1935 - Franz, Kyle R. (Labour / Le Travail, 2013)
The article reviews the book, "Labour at the Lakehead: Ethnicity, Socialism, and Politics, 1900-1935," by Michel S. Beaulieu.
Keywords: BEAULIEU, Michel S.; Canada; LABOUR at the Lakehead: Ethnicity, Socialism & Politics 1900-1935 (Book); Labor; Nonfiction

Giant Factories - Freeman, Joshua B. (Labour / Le Travail, 2013)
The article discusses the history of large factories from the Industrial Revolution in England to 21st-century China. Attention is drawn to the textile mills, iron and steel mills, and assembly lines depicted in the works of artists, photographers, writers, and cultural commentators. Labour militancy is also addressed. The conclusion ponders the future of large factories.
Keywords: BOURKE-White, Margaret, 1904-1971; CHINA; FACTORIES in art; FACTORIES in literature; Factories; History; TEXTILE factories; work

Montréal, l'avenir du passé: le dix-neuvième siècle - Frenette, Yves (Labour / Le Travail, 2013)
The article reviews the educational CD-ROM, "Montréal, l'avenir du passé: le dix-neuvième siècle," produced by Robert C. H. Sweeny and the organization Montréal, l'avenir du passé (MAP).
Keywords: Geography; MONTREAL (Quebec); TEACHING aids & devices

The Effects of a Training Levy on Training Characteristics and Outcomes: The Case of Quebec - Gagnon, Marie-Eve; Smith, Michael (Relations industrielles / Industrial Relations, 2013)
Much of the policy discussion on training is concerned with its undersupply. In 1995, inspired by the French example, Quebec introduced a levy on employers who underspend on training. In this paper we use a micro data set on Canadian workplaces to compare training characteristics and training effects on wages in Quebec with other parts of Canada. In Quebec, we find a much lower incidence of on-the-job training, a greater tendency to use outside trainers, and a larger effect of on-the-job training on wages. We speculate on ways in which these results may be explained by the training levy policy.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Training; Wages & salaries; Work environment

Le retour au travail lors d’un deuil périnatal : Des pratiques organisationnelles en porte-à-faux? - Gagnon, Mélanie; Beaudry, Catherine (Relations industrielles / Industrial Relations, 2013)
Cette recherche empirique qualitative de type exploratoire a pour objectif principal de lever le voile sur l’expérience de retour au travail d’employés vivant un deuil périnatal. Plusieurs recherches s’attachent à décrire et à étudier les conséquences d’un deuil périnatal chez les parents. Il est alors établi que le deuil périnatal se distingue des autres types de deuil, bien que l’intensité de la douleur vécue soit aussi importante. Pour l’heure, la littérature en ressources humaines se fait plutôt discrète sur la problématique du deuil périnatal spécifiquement en contexte de retour au travail. De fait, il devient nécessaire de référer à des études s’intéressant au retour au travail à la suite d’autres types de difficultés personnelles. À ce sujet, les écrits soulèvent trois catégories de facteurs influençant le retour au travail : les facteurs sociaux, organisationnels et individuels. L’importance de la perte que le deuil périnatal représente pour les parents endeuillés est souvent sous-estimée au sein des organisations. Lorsque les parents reviennent au travail après la perte de l’enfant à naître ou de leur nourrisson, ils sont fréquemment encore bien ancrés dans leur « processus de deuil » et d’adaptation à celui-ci. Or, le retour au travail dans le cadre d’un tel type de deuil est généralement peu encadré par les organisations. Cette étude fait donc état du vécu des employés en deuil au moment de leur réinvestissement en emploi. Afin d’explorer leur expérience, trois groupes de discussion ont été menés au Québec, avec des femmes ayant vécu la perte de leur enfant à naître ou de leur nourrisson.L’analyse de contenu a permis de conclure que la prise d’un congé à la suite du décès de l’enfant à naître ou du nourrisson, bien qu’importante, est insuffisante à elle seule, puisque lors de la reprise du travail, l’adaptation au deuil n’est pas terminée. Le facteur qui semble le plus déterminant au regard d’une réinsertion réussie s’avère le soutien que procurent les organisations par le biais de diverses pratiques, les plus importantes étant l’accès à un programme d’aide aux employés et l’aménagement du travail.
Keywords: deuil au travail; deuil périnatal; duelo en el trabajo; duelo perinatal; individual perspective; mourning and work; organizational practices; perinatal lost; perspectiva individual; perspective individuelle; pratiques organisationnelles; prácticas organizacionales; regreso al trabajo; retour au travail; return-to-work

La culture musicale des mineurs de Kirkland Lake : un premier aperçu - Gaudreau, Guy (Labour / Le Travail, 2013)
Cet article explore la culture musicale des mineurs de Kirkland Lake et en examine l’une de ses dimensions, celle exprimée par leurs pratiques de la musique, qu’elle soit symphonique ou populaire, chantée ou instrumentale, qu’elle se traduise par un concert ou qu’elle accompagne la danse ou les défilés. Connaissant les noms et les occupations de tout le personnel de deux des principales sociétés minières de la ville, la Lake Shore et la Wright-Hargreaves Gold Mines, nous avons cherché à savoir si les mineurs étaient reliés, d’une manière ou d’une autre, aux différentes manifestations musicales rapportées dans le journal local, le Northern News, tout au long de l’année 1934. Selon nous, la diversité des pratiques musicales observée s’expliquerait d’abord par la présence de nombreuses communautés ethniques parmi les mineurs mais aussi par des conditions de travail fort différentes, selon que le mineur travaille sous terre ou au jour.
Keywords: 20th century; Canada; ETHNIC groups; History; KIRKLAND Lake (Ont.); MINES & mineral resources; MINING corporations; MUSIC appreciation; MUSICIANS; Miners; Ontario

Parcours professionnels de femmes immigrées et de filles d'immigrés - Gauthier, Carol-Anne (Relations industrielles / Industrial Relations, 2013)
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Up Against the Wall: The Political Economy of the New Attack on the Canadian Labour Movement: A Reply to Andrew Jackson - Gindin, Sam (Just Labour: A Canadian Journal of Work and Society, 2013)

Labour Law and Union Recognition in Canada: A Historical-Institutionalist Perspective - Godard, John (Queen's Law Journal, 2013)
Despite the fact that the American Wagner model is the foundation of labour law in both Canada and the United States, that law has evolved in different ways in the two countries. The author argues that this can be accounted for by adopting a historical-institutionalist perspective, which explains differences by looking at formative historical conditions and the institutional norms and traditions to which they gave rise. The conditions and norms the author identifies in each country lead him to conclude that the Canadian and American Wagner models are driven by different underlying rationales: the American version is predominantly concerned with economic gain and limited state interference, whereas the Canadian version seeks to maintain order and stability through the exercise of state control. For the time being, Canada's version has proved more effective at sustaining higher levels of union density. The paper then asks what these differences might tell us about the future of labour law and unionization in Canada. The author argues that Wagnerism in Canada has been a double-edged sword. While it has given unions greater institutional security, that same security has discouraged labour leaders from pursuing meaningful reforms to avoid union decline. The author also observes that there has been an erosion of the distinct institutional norms and traditions that have historically prevailed in Canada, brought on by an ideological shift towards neo-liberalism and globalization. From a historical-institutionalist perspective, however, policies that deviate too far from a nation's historical trajectory are unlikely to survive for long.

Settling and Unsettling Memories: Essays in Canadian Public History - Gordon, Alan (Labour / Le Travail, 2013)
The article reviews the book, "Settling and Unsettling Memories: Essays in Canadian Public History," edited by Nicole Neatby and Peter Hodgins.
Keywords: Canada; HODGINS, Peter; NEATBY, Nicole; Nonfiction; PUBLIC history; SETTLING & Unsettling Memories: Essays in Canadian Public History (Book)

The Devil's Milk: A Social History of Rubber - Goutor, David (Labour / Le Travail, 2013)
The article reviews the book, "The Devil's Milk: A Social History of Rubber," by John Tully.
Keywords: DEVIL'S Milk: A Social History of Rubber, The (Book); History; Nonfiction; RUBBER; RUBBER industry; TULLY, John

Our Way to Fight: Peace-Work Under Siege in Israel-Palestine - Haiven, Judy (Labour / Le Travail, 2013)
The article reviews the book, "Our Way to Fight: Peace-Work Under Siege in Israel-Palestine," by Michael Riordon.
Keywords: ARAB-Israeli conflict -- Peace; Nonfiction; OUR Way to Fight: Peace-Work Under Siege in Israel-Palestine (Book); RIORDON, Michael

Research Handbook on the Future of Work and Employment Relations - Haiven, Judy (Relations industrielles / Industrial Relations, 2013)
Research Handbook on the Future of Work and Employment Relations, edited by Keith Townsend and Adrian Wilkinson, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Labor law; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Work environment

Work Stress and Coping in the Era of Globalization - Haiven, Judy (Relations industrielles / Industrial Relations, 2013)
Work Stress and Coping in the Era of Globalization, by Rabi S. Bhagat, James C. Segovis and Terry A. Nelson, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Cultural differences; Globalization; International; Labor Unions; Occupational stress; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

GRH et mondialisation : nouveaux contextes, nouveaux enjeux - Hallée, Yves (Relations industrielles / Industrial Relations, 2013)
The article reviews the book, "GRH et mondialisation : nouveaux contextes, nouveaux enjeux," edited by Didier Cazal, Éric Davoine, Pierre Louart and Françoise Chevalier.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Trajectoires des modèles nationaux : État, démocratie et travail en France et en Allemagne - Hanin, Frédéric (Relations industrielles / Industrial Relations, 2013)
The article reviews the book, "Trajectoires des modèles nationaux : État, démocratie et travail en France et en Allemagne," edited by Michel Dupré, Olivier Giraud and Michel Lallement.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Love and Struggle: My Life in SDS, the Weather Underground, and Beyond - Hannant, Larry (Labour / Le Travail, 2013)
The article reviews the book, "Love and Struggle: My Life in SDS, the Weather Underground, and Beyond," by David Gilbert.
Keywords: GILBERT, David; LOVE & Struggle: My Life in SDS, the Weather Underground & Beyond (Book); Nonfiction; WEATHER Underground Organization

The Life of Norman Bethune - Hannant, Larry (Labour / Le Travail, 2013)
The article reviews the book, "Phoenix: The Life of Norman Bethune," by Roderick Stewart and Sharon Stewart.
Keywords: BETHUNE, Norman, 1890-1939; Nonfiction; PHOENIX: The Life of Norman Bethune (Book); STEWART, Roderick; STEWART, Sharon

L’action collective au sein des alliances syndicales internationales : deux études de cas contrastées - Hennebert, Marc-Antonin; Dufour-Poirier, Mélanie (Relations industrielles / Industrial Relations, 2013)
Une des principales innovations syndicales en matière de régulation sociale des firmes transnationales réside dans l’émergence d’alliances syndicales internationales visant à fournir un espace de concertation et de développement de stratégies communes aux syndicats représentant les travailleurs d’une même firme. Sur la base de deux études de cas menées au sein de deux multinationales de différents secteurs et d’un corpus empirique incluant plus d’une centaine d’entretiens avec des syndicalistes de différents pays, cet article analyse la construction de l’action collective syndicale au sein de ces alliances. Partant de trois clés de lecture découlant d’autant de théories classiques de l’action collective – soit la théorie de la mobilisation des ressources, celle de la régulation sociale ainsi que celle dite de la structure d’opportunités politiques –, cet article met en relief certains facteurs déterminants du développement de cette action au sein des alliances syndicales internationales. Au-delà de l’importance pour les acteurs d’investir des ressources dans ces alliances, on observe que la formalisation organisationnelle de ces dernières, par l’intermédiaire de la définition de certaines règles d’organisation et la création de « centres » décisionnels, peut jouer un rôle déterminant dans leur propension à initier des actions collectives. Notre étude souligne également l’importance pour les acteurs syndicaux impliqués de définir un projet commun mobilisateur qui donne à la fois une cible et un sens aux actions planifiées. Au final, étant donné le bilan contrasté pouvant être tiré de ces deux cas, cet article met en lumière à la fois l’importante contribution potentielle de ces alliances au renouveau syndical mais aussi les nombreux obstacles qui se posent au développement de l’action syndicale internationale.
Keywords: cooperación inter-sindical; coopération intersyndicale; corporación multinacional; entreprises multinationales; inter-union cooperation; international labour regulation; international unionism; multinational corporation; regulación laboral internacional; régulation internationale du travail; sindicalismo internacional; syndicalisme international

The Real Dope: Social, Legal, and Historical Perspectives on the Regulation of Drugs in Canada - Heron, Craig (Labour / Le Travail, 2013)
The article reviews the book, "The Real Dope: Social, Legal, and Historical Perspectives on the Regulation of Drugs in Canada," edited by Edgar-André Montigny.
Keywords: Canada; DRUG laws & regulations; MONTIGNY, Edgar-Andre; Nonfiction; REAL Dope: Social, Legal & Historical Perspectives on the Regulation of Drugs in Canada, The (Book)

Handbook of Research in International Human Resource Management - Hodder, Andy (Relations industrielles / Industrial Relations, 2013)
The article reviews the book, "Handbook of Research in International Human Resource Management," 2nd edition, edited by Gunter K. Stahl.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Human resource management; International; Labor Unions; Management theory; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Up Against the Wall: The Political Economy of the New Attack on the Canadian Labour Movements - Jackson, Andrew (Just Labour: A Canadian Journal of Work and Society, 2013)
The Canadian labour movement faces an existential crisis. State and business hostility to unions is not new, but the attack has recently intensified as conservative political forces and major employer groups have embraced the agenda of the US Republican right. Mirroring anti-union US labour law would lead to the precipitous decline of union density in Canada, which is already eroding due to the manufacturing crisis and the long-standing failure of unions to organize in private services. The new attack is more a product of labour movement weakness than strength, and will be most effectively resisted by increasing union density and bargaining power in the private sector.

A Labour History of Ireland, 1824-2000 - James, Kevin J. (Labour / Le Travail, 2013)
The article reviews the book, "A Labour History of Ireland, 1824-2000," by Emmet O'Connor.
Keywords: LABOR movement -- History; LABOUR History of Ireland 1824-2000, A (Book); LABOUR Party (Ireland); Nonfiction; O'CONNOR, Emmet

Stalin's Man in Canada: Fred Rose and Soviet Espionage - Kealey, Gregory S. (Labour / Le Travail, 2013)
The article reviews the book, "Stalin's Man in Canada: Fred Rose and Soviet Espionage," by David Levy.
Keywords: Canada; Espionage; LEVY, David; Nonfiction; ROSE, Fred; STALIN'S Man in Canada: Fred Rose & Soviet Espionage (Book)

Obituary: Irene Whitfield - Kealey, Gregory S.; Cadigan, Sean (Labour / Le Travail, 2013)
Pays homage to Irene Whitfield (1941-2013), who was managing editor of the journal from 1982 to 2007.
Keywords: PERIODICAL editors; WHITFIELD, Irene

Showing Agency on the Margins: African American Railway Workers in the South and Their Unions, 1917-1930 - Kelly, Joseph (Labour / Le Travail, 2013)
During World War I and the 1920s, African American trainmen throughout the South took advantage of federal administrative bodies that had set anti-discrimination rules to challenge racist employers and white trainmen alike. After the war, white workers insisted that African Americans be relegated to porter jobs. White employers demanded that African American workers who continued to work as brakemen and flagmen, as they had during the war, accept lower wages for such skilled work than their white counterparts were paid. The federal government preferred to turn a blind eye to racial discrimination against African American workers in the period after federal control of the railways ended. Despite this concerted attack from all sides on their rights, unions of African American trainmen continued their fight, with some success, before federal administrative tribunals as well as the courts to retain skilled positions and receive the same pay as their white equivalents. Only the devastation of rail jobs in the 1930s largely destroyed the African American trainmen's wartime gains.
Keywords: 20th century; AFRICAN Americans -- Employment; Equal pay for equal work; History; LABOR laws & legislation; LABOR unions -- United States; PORTERS; RACE discrimination -- United States; RACE discrimination in employment; RAILROAD construction workers; RAILROADS -- United States; United States; WAGES -- Railroads

The Impact of Social Networks on Labour Market Outcomes: New Evidence from Cape Breton - Khan, Adnan Q.; Lehrer, Steven F. (Canadian Public Policy, 2013)
Debates centered on the role of social networks as a determinant of labour market outcomes have a long history in economics and sociology; however, determining causality remains a challenge. In this study we use information on random assignment to a unique intervention to identify the impact of changes in the size of alternative social network measures on subsequent employment at both the individual and community levels. Our results indicate that being assigned to the treatment protocol significantly increased the size of social networks, particularly weak ties. Nevertheless, these increases do not translate into improved employment outcomes 18 months following study completion. We do not find any evidence of treatment effect heterogeneity based on the initial size of one’s social network; rather those whose strong ties increased at a higher rate during the experiment were significantly less likely to hold a job following the experiment. We find that many of these results also hold at the community level among those who did not directly participate in the intervention. In summary, our results suggest that policies can successfully influence the [End Page S1] size of an individual’s social network, but that these increases have a limited impact on long-run labour market outcomes, with the notable exception of changes in the composition of individuals who hold jobs.

Du côté des vainqueurs : une sociologie de l'incertitude sur les marchés du travail - Kirouac, Laurie (Relations industrielles / Industrial Relations, 2013)
The article reviews the book, "Du côté des vainqueurs : une sociologie de l’incertitude sur les marchés du travail," by François Sarfati.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Game Plan: A Social History of Sport in Alberta - Kossuth, Robert S. (Labour / Le Travail, 2013)
The article reviews the book, "Game Plan: A Social History of Sport in Alberta," Karen L. Wall.
Keywords: Alberta; Canada; GAME Plan: A Social History of Sport in Alberta (Book); History; Nonfiction; Sports; WALL, Karen L.

Relentless Change: A Casebook for the Study of Canadian Business History - Krats, Peter V. (Labour / Le Travail, 2013)
The article reviews the book, "Relentless Change: A Casebook for the Study of Canadian Business History," edited by Joe Martin.
Keywords: Business; Canada; History; MARTIN, Joe; Nonfiction; RELENTLESS Change: A Casebook for the Study of Canadian Business History (Book)

Revitalizing Union Action: The Impact Of Youth Committees In A Public Sector Labour Federation In Québec - Laroche, Mélanie; Dufour-Poirier, Mélanie (Just Labour: A Canadian Journal of Work and Society, 2013)
This article examines the revitalization of a union federation's capacity to represent young workers. It presents a qualitative study of the role and impact of one of the most developed forms of youth involvement in a union, youth committees. It first analyzes the extent to which these committees helped put the concerns of members under the age of 30 on the union federation's agenda and fostered their participation in its internal life. Second, it examines the ways in which these committees initiated a degree of change in the federation at the institutional level. Overall, our findings indicate that youth committees were able to question existing practices and initiate a degree of union change. However, the disagreements expressed by the young workers tended to remain confined within these parallel structures, thus limiting their potential to change the representative capacity of the federation.

Brève histoire du régime seigneurial - Larose, André (Labour / Le Travail, 2013)
The article reviews the book, "Brève histoire du régime seigneurial," by Benoît Grenier.
Keywords: BREVE histoire du regime seigneurial (Book); Canada; GRENIER, Benoit; History; MANORIALISM; Nonfiction; TO 1763 (New France)

Développement des identités, des compétences et des pratiques professionnelles - Le Capitaine, Catherine (Relations industrielles / Industrial Relations, 2013)
The article reviews the book, "Développement des identités, des compétences et des pratiques professionnelles," edited by Anne-Marie Vonthron, Sabine Pohl and Pascale Desrumaux.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Les conditions de travail au Québec : Une analyse différenciée selon les groupes d’âge - Ledoux, Élise; Fournier, Pierre-Sébastien; Champoux, Danièle; Prud’homme, Pascale; Laberge, Marie; Aurousseau, Chantal; Ouellet, Sylvie; Chatigny, Céline (Relations industrielles / Industrial Relations, 2013)
Cet article présente les travaux d’une communauté de chercheurs du Réseau de recherche en santé et en sécurité du travail du Québec (RRSSTQ), créée en 2006, laquelle s’intéresse aux questions d’âges et de rapports sociaux en milieux de travail, en lien avec les conditions de travail et la santé et la sécurité du travail. De disciplines diverses (ergonomie, sociologie, psychosociologie, communication, droit, éducation), cette communauté réalise des recherches à partir d’enquêtes et d’études de terrain s’appuyant sur une approche compréhensive des phénomènes. Cette problématique se situe dans un contexte social singulier marqué, entre autres, par la mondialisation des marchés, une introduction massive des nouvelles technologies, une transformation des formes d’emploi, ainsi qu’un vieillissement de la main-d’oeuvre dans les pays industrialisés. Ces transformations créent des conditions particulières de rétention et d’intégration de la main-d’oeuvre dans les milieux de travail. À partir des données de l’Enquête québécoise sur des conditions de travail, d’emploi et de santé et de sécurité du travail (EQCOTESST), réalisée en 2008, auprès d’un échantillon représentatif de 5 071 répondants, l’objectif de cette étude est de tracer un portrait des conditions de travail en fonction de l’âge des travailleurs au Québec. L’article propose l’interprétation de ce portrait à partir d’un cadre d’analyse s’appuyant sur une approche diachronique des dynamiques âge-travail-santé dans le but de mieux orienter les interventions en milieu de travail.
Keywords: age; approche diachronique; condiciones de empleo; condiciones de trabajo; condition de travail; condition d’emploi; diachronic approach; edad; employment conditions; enfoque diacrónico; trajectoires; trajectories; trayectorias; work conditions; âge

In Pursuit of Gold: Chinese American Miners and Merchants in the American West - Lew-Williams, Beth (Labour / Le Travail, 2013)
The article reviews the book, "In Pursuit of Gold: Chinese American Miners and Merchants in the American West," by Sue Fawn Chung.
Keywords: 19th century; CHINESE -- United States; CHUNG, Sue Fawn; GOLD mines & mining -- History; History; IN Pursuit of Gold: Chinese American Miners & Merchants in the American West (Book); Nonfiction

Has There Been a She-covery? The Financial Crisis of 2008 and Its Impact on the Ontario Labour Market - Lewchuk, Wayne (Relations industrielles / Industrial Relations, 2013)
This paper explores changes in labour market outcomes between June 2005 and November 2010. It asks if the recovery in labour markets following the 2008 financial crisis favoured men or women. The analysis is based on a unique longitudinal database of individuals in the Toronto-Hamilton labour market. Men were the most likely to have paid employment in the post-financial crisis period, but only at the cost of a significant deterioration in its terms and conditions. The findings suggest that many middle-aged workers were not protected by job seniority or implicit lifetime employment relationships. The findings point to a further decline in the prevalence of the standard employment relationship and the male breadwinner model of employment.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Economic recovery; Employment; LABOR market; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

A New Union for Challenging Times: A Reply to Andrew Jackson - Lewenza, Ken (Just Labour: A Canadian Journal of Work and Society, 2013)

The Intersecting Dynamics of Social Exclusion: Age, Gender, Race and Immigrant Status in Canada's Labour Market - Lightman, Naomi; Gingrich, Luann Good (Canadian Ethnic Studies, 2013)
Through the use of a social exclusion framework and analysis of recent data from the Survey of Labour and Income Dynamics (2009), a national longitudinal database, this empirical research investigates the mechanisms through which social groups are made and socio-economic outcomes are determined in Canada today. Our objective is to explore and describe the social characteristics and personal attributes that intersect to direct divergent economic realities. To this end, we initially present a brief review of the social exclusion literature, as well as descriptive data on several aspects of age and immigration. This is followed by logistic regressions for five dimensions of economic exclusion, to examine who is made socially excluded in economic terms in Canada. Subsequently, to progress the analysis from a focus on the individual effects of specific social attributes, we calculate the combined odds of two dimensions of economic exclusion (low individual earnings and insecure employment) for eight prototypes of individuals, to highlight the intersecting effects of social dynamics related to age, gender, visible minority status and immigrant status, and to ultimately explore who gets ahead and who falls behind in the Canadian labour market. We conclude with a discussion of policy and research implications.

Private-Sector Pension Plans: Have Recent Pension Reforms Addressed the Needs of Plan Sponsors - Litner, Paul W.; Marin, Jonathan (Canadian Labour and Employment Law Journal, 2013)
Defined benefit (DB) pension plans have historically been an import- ant element in Canada's "three pillar" retirement income system. However, recessions in the global and Canadian economies have increased pressures on the funding of DB plans, and highlighted concerns about their sustainability - developments which have prompted governments in Canada to introduce a num- ber of reforms to pension benefit legislation. The authors, counsel to employers and plan sponsors, provide an overview of the existing legislation and the reform process, with particular emphasis on changes to Ontario's regulatory framework for DB plans as it relates to four key areas: plan solvency andfunding, surpluses, partial plan wind-ups, and asset transfers and plan mergers or splits. The paper notes that many if not all of these measures have been well-received by plan sponsors. However, in assessing whether the reforms will have the intended effect of stemming the decline in DB plan participation, the authors question whether the measures taken so far are not "too little, too late," and suggest that more far-reaching, and permanent, steps will be necessary. The paper also reviews and comments on the main features of the legislation recently enacted by the federal government providing for pooled registered pension plans.

Flexibility at the Core: What Determines Employment of Part-Time Faculty in Academia - Liu, Xiangmin; Zhang, Liang (Relations industrielles / Industrial Relations, 2013)
This study uses both institutional and individual level data to examine the variation of part-time faculty employment in colleges and universities in the United States. Results support the arguments that higher educational institutions actively adopt contingent work arrangements to manage their resource dependence with constituencies, to save on labour costs, and to maximize academic prestige. Private institutions, on average, have higher levels of part-time faculty than their public counterparts. The proportion of part-time students and the share of institutional revenues derived from tuition and fees are positively associated with part-time faculty employment. Institutions that have limited resource slack and pay high salaries to their full-time faculty members tend to employ a high proportion of part-time faculty.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Cost reduction; Labor Unions; Part time employment; Revenue; School faculty; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; higher education

Negotiating Narratives: Recent Approaches in Consumer Studies - Liverant, Bettina (Labour / Le Travail, 2013)
The article reviews and comments on the books "Debtor Nation: The History of America in Red Ink," by Louis Hyman, "Packaging Pleasure: Holiday Camps in Twentieth-Century Britain," by Sandra Dawson, and "Consumption and Its Consequences," by Daniel Miller.
Keywords: CONSUMPTION & Its Consequences (Book); DAWSON, Sandra; DEBTOR Nation: The History of America in Red Ink (Book); HYMAN, Louis, 1977-; MILLER, Daniel; Nonfiction; PACKAGING Pleasure: Holiday Camps in 20th-Century Britain (Book)

Le transfert de connaissances au RRSSTQ : Bilan et perspectives - Lortie, Monique; Desmarais, Lise; Faye, Cheikh; Laroche, Éléna; Faurie, Isabelle (Relations industrielles / Industrial Relations, 2013)
Cet article a pour objectif de poser un regard rétrospectif sur les activités scientifiques et les réflexions menées par le regroupement stratégique en transfert de connaissances (RS-TC) afin de dégager des axes de développement sur ce thème en lien avec la santé et sécurité au travail (SST). Afin de dresser ce bilan, nous avons effectué une analyse documentaire à partir de deux sources principales : 1) les activités de type symposiums et tables rondes organisées successivement en 2005, 2006, 2008, 2010 et 2011 et les diverses présentations et publications qui en sont issues et 2) les revues de littérature effectuées sur le transfert des connaissances en SST. Nous présentons d’abord un bref portrait des activités de transfert en SST réalisées par le RS-TC du Réseau de recherche en santé et sécurité du travail (RRSSTQ). Par la suite, nous proposons diverses pistes de réflexion développées à partir des activités menées depuis la création de ce regroupement au sein du RRSSTQ. Par exemple, le piège de restreindre le sens du terme connaissance et de s’y astreindre, le choix d’un intitulé représentatif de la question du transfert au Réseau, la nécessité d’opérer une double articulation individu/organisation, l’importance et la complexité du rôle des relayeurs, la multiplicité des outils de relais, la problématique de l’implantation. Nous terminons sur une piste de réflexion encore inexplorée par la communauté de chercheurs en TC de ce regroupement – les décideurs, auxquels peu d’efforts ont été consacrés – et sur les suites à donner au travail réalisé à ce jour : développer un cadre d’analyse propre à rendre compte des savoirs et savoir-faire développés au Réseau.
Keywords: agentes de relevo; formaciones; formations; guides; guías; intermediaries; knowledge; knowledge transfer; relayeurs; saberes; savoirs; training; transferencia de conocimientos; transfert des connaissances

Reds at the Blackboard: Communism, Civil Rights, and the New York City Teachers Union - Lyons, John F. (Labour / Le Travail, 2013)
The article reviews the book, "Reds at the Blackboard: Communism, Civil Rights, and the New York City Teachers Union," by Clarence Taylor.
Keywords: COMMUNISM & education; NEW York (State); Nonfiction; REDS at the Blackboard: Communism, Civil Rights & the New York City Teachers Union (Book); TAYLOR, Clarence; TEACHERS' unions

Hearts and Minds: Canadian Romance at the Dawn of the Modern Era, 1900-1930 - Macdonald, Heidi (Labour / Le Travail, 2013)
The article reviews the book, "Hearts and Minds: Canadian Romance at the Dawn of the Modern Era, 1900-1930," by Dan Azoulay.
Keywords: AZOULAY, Dan; HEARTS & Minds: Canadian Romance at the Dawn of the Modern Era 1900-1930 (Book); History; Nonfiction; ROMANTIC love

Labour and the Commemorative Landscape in Industrial Cape Breton, 1922-2013 - MacKinnon, Lachlan (Material Culture Review, 2013)
Labour landmarks are monuments, memorials, plaques and other sites that commemorate the past experiences of workers in society. These sites are also manifestations of the collective memory of labourers. In industrial Cape Breton, which has a long history of labour and class struggle, an analytical survey of labour landmarks reveals how the industrial past has been remembered and memorialized. This overview reflects the narratives that have been attached to these sites, the ways in which historical memory has been localized and constructed in industrial Cape Breton, and the new layers of meaning that are revealed as these communities transition into post-industrialism.

"To Those Who Lost Their Lives": Reading a Labour Landmark in Sydney, Nova Scotia - MacKinnon, Lachlan (Labour / Le Travail, 2013)
Discusses the importance of labour landmarks, in particular the United Steelworker's Memorial Monument in Sydney, Nova Scotia. Provides the historical context of labour unrest and industrial fatalities that occurred at the Sydney steelplant, with summaries of the circumstances that resulted in the deaths of individual workers over the decades. Takes note of ownership changes, advances in workplace safety through unionism, and the plant's toxic legacy.
Keywords: COLLECTIVE memory; History; Labor Unions; STEEL industry -- History; SYDNEY (N.S.); UNITED Steelworkers of America; Workers' monuments

Two-Tier Workplace Compensation: Issues and Remedies - MacNeil, Michael (Canadian Labour and Employment Law Journal, 2013)
As a result of the recession that began in 2008, many employers are look- ing for ways to cut labour costs. One way of doing so is to impose two-tier compensation schemes, whereby younger employees do essentially the same job as older ones, but for lower wages and benefits. The key concern of this paper is how Canadian labour, employment and human rights law could respond to the differential impact of two-tier schemes on younger workers. First, the author reviews the use of two-tier systems in the United States and Canada, showing that they affect not only workers' wages and benefits but also their pensions, as employers move from defined benefit to defined contribution plans. In the next part of the paper, he analyses arbitral, labour board and human rights tribunal case law, arguing that lower-tier workers face significant barriers in seeking legal recourse through duty of fair representation or human rights complaints. The author concludes with an overview of the restrictions on two-tier schemes in the Quebec employment standards statute, and discusses the difficulties of enacting similar legislation in other Canadian jurisdictions.

Acquired Expertise of Administrative Tribunals and the Standard of Judicial Review: The Case of Grievance Arbitrators and Human Rights Law - Makela, Finn (Canadian Labour and Employment Law Journal, 2013)
Focusing on arbitral decisions on human rights claims arising in the employment context, this paper looks at the nature of the expertise of adminis- trative tribunals and its role in determining the standard of judicial review. The author notes that arbitrators are considered to have expertise in labour rela- tions, and that this has been a key factor in the high level of deference generally shown by courts to their decisions. However, despite the expansion of arbitral jurisdiction over human rights matters in unionized workplaces, the courts, applying a "correctness" standard of review, have refused to grant deference to arbitrators with respect to their interpretation and application of human rights legislation, in part on the basis that they are not expert in the area. The author takes issue with this view, contending that arbitrators have in fact acquired significant expertise in interpreting human rights statutes in the context of the employment relationship, and that recognition of such expertise should lead to a reappraisal of the level of curial deference. In this regard, he argues, it would be open to the courts to deem arbitrators to possess the requisite expertise in human rights, thereby justifying a more deferential "reasonableness" standard of review.

Créativité et gestion : les idées au service de l'innovation - Malo, François Bernard (Relations industrielles / Industrial Relations, 2013)
Créativité et gestion : les idées au service de l’innovation, by Camille Carrier et Sylvie Gélinas, is reviewed.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

The Tailor of Ulm: Communism in the Twentieth Century - Manley, John (Labour / Le Travail, 2013)
The article reviews the book, "The Tailor of Ulm: Communism in the Twentieth Century," by Lucio Magri.
Keywords: 20th century; Communism; History; MAGRI, Lucio, 1932-2011; Nonfiction; TAILOR of Ulm: Communism in the 20th Century, The (Book)

Combating Mountaintop Removal: New Directions in the Fight Against Big Coal - Manuel, Jeffrey T. (Labour / Le Travail, 2013)
The article reviews the book, "Combating Mountaintop Removal: New Directions in the Fight Against Big Coal," by Bryan T. McNeil.
Keywords: COAL mines & mining; COMBATING Mountaintop Removal: New Directions in the Fight Against Big Coal (Book); MCNEIL, Bryan T.; MOUNTAINTOP removal mining; Nonfiction; WEST Virginia

Research Handbook of Comparative Employment Relations - Markey, Raymond (Relations industrielles / Industrial Relations, 2013)
Research Handbook of Comparative Employment Relations, edited by Michael Barry and Adrian Wilkinson, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Labor relations; Political economy; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Contesting White Supremacy: School Segregation, Anti-Racism and the Making of Chinese Canadians - Marshall, Alison R. (Labour / Le Travail, 2013)
The article reviews the book, "Contesting White Supremacy: School Segregation, Anti-Racism and the Making of Chinese Canadians," by Timothy J. Stanley.
Keywords: ANTI-racism; CONTESTING White Supremacy: School Segregation, Anti-Racism & the Making of Chinese Canadians (Book); Chinese Canadians; History; Nonfiction; STANLEY, Timothy J.

Pierre Laporte - Martel, Marcel (Labour / Le Travail, 2013)
The article reviews the book, "Pierre Laporte," by Jean-Charles Panneton.
Keywords: LAPORTE, Pierre Francois, 1799-1841; Nonfiction; PANNETON, Jean-Charles; PIERRE Laporte (Book)

Remaking E.P. Thompson - Matthews, Wade (Labour / Le Travail, 2013)
The article reviews and comments extensively on the book, "The Crisis of Theory: E. P. Thompson, the New Left and Postwar British Politics," by Scott Hamilton.
Keywords: CRISIS of Theory: E.P. Thompson, the New Left & Postwar British Politics, The (Book); HAMILTON, Scott; Nonfiction; THOMPSON, E. P. (Edward Palmer), 1924-1993

"Telford Time" and the Populist Origins of the CCF in British Columbia - McDonald, Robert A. J. (Labour / Le Travail, 2013)
The article focuses on the Canadian political party the Co-operative Commonwealth Federation (CCF) in British Columbia (BC) and how it promoted populism and socialism within the province during the 1930s. The author explores the role of party founder Lyle Telford in the CCF movement, discusses how the CCF won the provincial vote in 1933, and examines the CCF's successor party the New Democratic Party (NDP).
Keywords: BRITISH Columbia -- Politics & government -- 20th century; CO-Operative Commonwealth Federation (Political party : Canada); Canada; History; NEW Democratic Party (Political party : British Columbia); Political parties; Socialism; TELFORD, Lyle; elections; populism

Beyond Blood: Rethinking Indigenous Identity - Miller, J. R. (Labour / Le Travail, 2013)
The article reviews the book, "Beyond Blood: Rethinking Indigenous Identity," by Pamela D. Palmater.
Keywords: BEYOND Blood: Rethinking Indigenous Identity (Book); ETHNIC identity; Indigenous Peoples; Nonfiction; PALMATER, Pamela D.

The Invisible Handcuffs of Capitalism: How Market Tyranny Stifles the Economy by Stunting Workers - Milloy, Jeremy (Labour / Le Travail, 2013)
The article reviews the book, "The Invisible Handcuffs of Capitalism: How Market Tyranny Stifles the Economy by Stunting Workers," by Michael Perelman.
Keywords: Capitalism; Economic aspects; INVISIBLE Handcuffs of Capitalism: How Market Tyranny Stifles the Economy by Stunting Workers, The (Book); Nonfiction; PERELMAN, Michael

Negotiating Neoliberal Empowerment: Aboriginal People, Educational Restructuring, and Academic Labour in the North of British Columbia, Canada - Mills, Suzanne E.; McCreary, Tyler (Antipode, 2013)
Aboriginal peoples in Canada are gaining influence in post-secondary education through Aboriginal-directed programs and policies in non-Aboriginal institutions. However, these gains have occurred alongside, and in some cases through, neoliberal reforms to higher education. This article explores the political consequences of the neoliberal institutionalization of First Nations empowerment for public sector unions and workers. We examine a case where the indigenization of a community college in British Columbia was embedded in neoliberal reforms that ran counter to the interests of academic instructors. Although many union members supported indigenization, many also possessed a deep ambivalence about the change. Neoliberal indigenization increased work intensity, decreased worker autonomy and promoted an educational philosophy that prioritized labour market needs over liberal arts. This example demonstrates how the integration of Aboriginal aspirations into neoliberal processes of reform works to rationalize public sector restructuring, constricting labour agency and the possibilities for alliances between labour and Aboriginal peoples.
Keywords: education; indigenous peoples; restructuring; union; work

On Agency, Freedom, and the Boundaries of Slavery Studies - Millward, Jessica (Labour / Le Travail, 2013)
The article reviews and comments on several books including "From Africa to Jamaica: The Making of an Atlantic Slave Society, 1775-1807," by Audra A. Diptee, "Gleanings of Freedom: Free and Slave Labor Along the Mason-Dixon Line, 1790-1860," by Max Grivno, and "Forging Freedom: Black Women and the Pursuit of Liberty in Antebellum Charleston," by Amrita Chakrabarti Myers.
Keywords: DIPTEE, Audra A.; FORGING Freedom: Black Women & the Pursuit of Liberty in Antebellum Charleston (Book); FROM Africa to Jamaica: The Making of an Atlantic Slave Society 1775-1807 (Book); GLEANINGS of Freedom: Free & Slave Labor Along the Mason-Dixon Line 1790-1860 (Book); GRIVNO, Max; MYERS, Amrita Chakrabarti; Nonfiction

A Life in Balance? Reopening the Family-Work Debate - Morris, Marika (Labour / Le Travail, 2013)
The article reviews the book, "A Life in Balance? Reopening the Family-Work Debate," edited by Catherine Krull and Justyna Sempruch.
Keywords: KRULL, Catherine; LIFE in Balance? Reopening the Family-Work Debate, A (Book); Nonfiction; SEMPRUCH, Justyna; WORK-life balance

A Bridge of Ships: Canadian Shipbuilding during the Second World War - Muhammad, Robin Dearmon (Labour / Le Travail, 2013)
The article reviews the book. "A Bridge of Ships: Canadian Shipbuilding during the Second World War," by James Pritchard.
Keywords: BRIDGE of Ships: Canadian Shipbuilding During the Second World War, A (Book); Canada; Nonfiction; PRITCHARD, James; Shipbuilding

Babies for the Nation: The Medicalization of Motherhood in Quebec, 1910-1970 - Mullally, Sasha (Labour / Le Travail, 2013)
The article reviews the book, "Babies for the Nation: The Medicalization of Motherhood in Quebec, 1910-1970," by Denyse Baillargeon, translated by W. Donald Wilson.
Keywords: BABIES for the Nation: The Medicalization of Motherhood in Quebec 1910-1970 (Book); BAILLARGEON, Denyse; Canada; MATERNAL health services; MEDICALIZATION; Nonfiction

Workplace Representatives: Strategic Actors of Union Renewal?: Workplace Representatives and Union Renewal - Murray, Gregor; Lévesque, Christian; Dufour, Christian; Hege, Adelheid (Industrial Relations Journal, 2013)
Workplace representatives (shop stewards) provide insight into union transformations. This article explores the renewed research interest in terms of the representativeness of unionism and of workplace representatives, the complexity of the sites of representation and employer strategies, the search for new references and the centrality of workplace representatives in union renewal strategies.

Improving Organizational Interventions for Stress and Well-being - Muurlink, Olav (Relations industrielles / Industrial Relations, 2013)
Improving Organizational Interventions for Stress and Well-being, edited by Caroline Biron, Maria Karanika-Murray and Cary L. Cooper, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Job satisfaction; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Stress; Work life balance

From Serious Shortage of Researchers to OHS Law Changes and Growing Industrial Needs: A Dynamic and Quiet Force - Nadeau, Sylvie; Fatisson, Julien; Badri, Adel; Emami-Mehrgani, Behnam (Relations industrielles / Industrial Relations, 2013)
An initial observation by the work safety research community of the Quebec Occupational Health and Safety Research Network (QOHSRN) reveals that occupational safety, an aspect affecting all industrial sectors, requires international exchanges to meet the objectives and expand the knowledge gained within the network. This historical review is also meant to show the diversity of the work safety research community goals and the need to develop intersectoral research projects. The growing and essential involvement of student members within the research community ensures a solid future in that regard.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Historical analysis; Knowledge management; Labor Unions; Occupational safety; Reforms; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

In the Interest of Democracy: The Rise and Fall of the Early Cold War Alliance Between the American Federation of Labor and the Central Intelligence Agency - Nastovski, Katherine (Labour / Le Travail, 2013)
The article reviews the book, "In the Interest of Democracy: The Rise and Fall of the Early Cold War Alliance Between the American Federation of Labor and the Central Intelligence Agency," by Quenby Olmsted Hughes.
Keywords: AMERICAN Federation of Labor; COLD War, 1945-1989 -- Political aspects; HUGHES, Quenby Olmsted; IN the Interest of Democracy: The Rise & Fall of the Early Cold War Alliance Between the American Federation of Labor & the Central Intelligence Agency (Book); Nonfiction

The British Columbia CCF's Working-Class Moment: Socialism Not Populism - Naylor, James (Labour / Le Travail, 2013)
The article focuses on the Canadian political party the British Columbia Co-operative Commonwealth Federation (BC/CCF) and how it contributed to a political left-wing social movement for Canada's working class during the 1930s. The author argues that while the BC/CCF had populist beginnings, it was truly a socialist party. He discusses how the BC/CCF impacted Canadian politics during the interwar years, argues that the party created an anti-liberal movement, and explores the BC/CCF's relationship to the Socialist Party of Canada.
Keywords: 20th century; BRITISH Columbia -- Politics & government -- 20th century; CANADA -- Politics & government -- 1914-1945; CO-Operative Commonwealth Federation (Political party : Canada); Canada; History; LEFT & right; Liberalism; Political parties; Social movements; Socialism; Socialist Party of Canada; WORKING class -- Political activity; populism

The Legal In/Security of Temporary Migrant Agricultural Work: Case Studies from Canada and Australia - Newman, Andrew (Deakin Law Review, 2013)
Despite differing labour law systems and program structures, temporary migrant agricultural workers under the Canadian Seasonal Agricultural Worker Program and Australian Seasonal Worker Program often possess minimal security of employment rights and protections, despite potentially lengthy periods of consecutive seasonal service to the same employer. Such lesser rights and protections are partly due to the central role played by continuity of service in determining the length of reasonable notice periods and the strength of unfair dismissal protections and stand-down/recall rights. Although it is often presumed that the temporary duration of the seasonal work visa necessarily severs the legal continuity of the employment relationship, such is not the case. This article argues that security of employment rights and protections can be re-conceptualised to recognise non-continuous seasonal service within the current parameters of a fixed-term work visa. In both Canada and Australia this could be accomplished through contractual or collective agreement terms or through the amendment of labour law legislation. Such reforms would recognise a form of unpaid 'migrant worker leave', whereby the legal continuity of employment would be preserved despite periods of mandatory repatriation, thus allowing accrual of security of employment rights and protections.
Keywords: Australia; Canada; Labor laws and legislation; Seasonal Agricultural Workers Program

Memorial of War, Memorial of Hope: Contemplating the creation, destruction, and re-creation of Fred Ross' mural The Destruction of War/Rebuilding the World Through Education, 1948,1954, and 2011 - Niergarth, Kirk (Labour / Le Travail, 2013)
The article is an extensive commentary on the history and significance of the mural, "The Destruction of War/Rebuilding the World Through Education," by Fred Ross. The mural was painted in the late 1940s at Fredericton High School in Fredericton, N.B. Removed in the 1950s, it was subsequently lost. A recreated version of the mural was installed at the University of New Brunswick in 2011.
Keywords: COLD War, 1945-1989; History; LOST works of art; MURAL painting & decoration -- 20th century; New Brunswick; ROSS, Fred; WORLD War, 1939-1945 -- Art & the war

The Historical and Contemporary Life-Value of the Canadian Labour Movement - Noonan, Jeff (Labour / Le Travail, 2013)
Neo-liberal ideology has attempted to set different groups of workers--employed and unemployed, public and private sector, unionized and non-unionized--in opposition to each other. A successful response will require more than clear philosophical principles. It will require detailed, difficult, and long-term political efforts to construct solidarity. At the same time, that practical political work requires principles. The most effective principles on the basis of which solidarity can be built are those that disclose shared interests. The life-value principles underlying the most significant achievements of the union movement are the best means by which the shared interests of all workers can be disclosed. (English)
Keywords: CANADA -- Economic conditions -- 1991-; Canada; EMPLOYMENT (Economic theory); Employees; LABOR market; Labor Unions; Labor movement; Neoliberalism; SOLIDARITY; STRIKES & lockouts; Unemployment

Filipino Health Care Aides and the Nursing Home Labour Market in Winnipeg - Novek, Sheila (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2013)
Canada’s nursing homes have become increasingly dependent on immigrant health care aides. More than any other ethnic group, Filipino women are over-represented among health care aides in the Canadian health care system. This qualitative study explored the employment experiences of Filipino health care aides in nursing homes from their own perspectives as well as those of policy stakeholders. Fourteen in-depth interviews were conducted with Filipino health care aides and long-term-care policy stakeholders in Winnipeg, Manitoba. The results indicated that migrant social networks act as pathways linking immigrant women with employment opportunities in nursing homes. The composition of the labour force is also shaped by management strategies and labour market accommodations that respond to, and reinforce, these social networks. These findings have implications for workforce planning and the quality of care provision in nursing homes.

Valuing Care Work: Comparative Perspectives - Nyland, Chris (Relations industrielles / Industrial Relations, 2013)
The article reviews the book, "Valuing Care Work: Comparative Perspectives," edited by Cecilia Benoit and Helga Hallgrimsdottir.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Caregivers; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social policy; Welfare

Pitching for Each Others' Team: The North American Free Trade Agreement and Labor Transnationalism - Ozarow, Daniel (Labor History, 2013)
The North American Free Trade Agreement's side accord – the 1994 North American Agreement on Labor Cooperation – has been portrayed as providing an ineffective, bureaucratic procedure for dealing with labor complaints about infringements of national labor legislation. This paper reviews two decades of experience. It argues that after an initial period of formal activity, which did indeed expose the accord's severe limitations, a new era of intensified international links at grassroots level commenced. Despite its limitations, the accord initiated positive learning processes and intensified exchanges between the trade union movements in the USA, Canada and Mexico.
Keywords: INTERNATIONAL labor activities; LABOR movement -- Canada; LABOR movement -- Mexico; LABOR movement -- United States; NORTH American Agreement for Labor Cooperation (Organization); NORTH American Free Trade Agreement (NAFTA); Transnationalism

Navigating the Productive/Reproductive Split: Latin American Transnational Mothers and Fathers in Canada's Temporary Migration Programs - Paciulan, Melissa; Preibisch, Kerry (Transnational Social Review, 2013)
This article explores the experiences of transnational agricultural migrant workers in Canada's guestworker programs. Examined through a gendered lens, it focuses on migrants' experiences as parents to children whom they must leave behind in their communities of origin when they migrate. Drawing on interview and ethnographic data, this article argues that transnational parents, especially mothers, face a unique set of challenges and barriers as participants in these programs. It explores how the injustices in the immigration-labor regime that migrants confront as racialized, non-citizen farm workers impact parents' ability to focus on their primary motivation to migrate—their children—thereby limiting their ability to fulfill idealized forms of motherhood and fatherhood and hindering their parent-child relationships. It also demonstrates that migrant mothers frequently experience increased feelings of self-doubt, guilt and inadequacy as transnational parents, which, in turn, diminishes the benefits of their migration.

Sasha and Emma: The Anarchist Odyssey of Alexander Berkman and Emma Goldman - Palmer, Bryan D. (Labour / Le Travail, 2013)
The article reviews the book, "Sasha and Emma: The Anarchist Odyssey of Alexander Berkman and Emma Goldman," by Paul Avrich and Karen Avrich.
Keywords: AVRICH, Karen; AVRICH, Paul; BERKMAN, Alexander, 1870-1936; GOLDMAN, Emma, 1869-1940; Nonfiction; SASHA & Emma: The Anarchist Odyssey of Alexander Berkman & Emma Goldman (Book)

The Making of the English Working Class at Fifty - Palmer, Bryan D.; Chakrabarty, Dipesh; Eley, Geoff; McCallum, Todd; Epstein, James; Carbonella, August; Tremblay, Robert; Fahrni, Magda; Lemisch, Jesse; Kessler-Harris, Alice; Hannam, June (Labour / Le Travail, 2013)
Introduces the second of the two-part series in the journal on the 50th anniversary of the publication of "The Making of the English Working Class" by E.P. Thompson. Articles include: "The Lost Causes of E. P. Thompson" by Dipesh Chakrabarty; "Class Formation, Politics, Structures of Feeling" by Geoff Eley; "Comrade Thompson and Saint Foucault" by Todd McCallum; "Exploitation: A Useful Category of Historical Analysis?" by James Epstein; "Looking Back and Ahead" by August Carbonella; "The Making dans les eaux troubles de l’historiographie québécoise : réception hésitante d’un livre en avant de son temps" by Robert Tremblay; "Who now reads E.P. Thompson? Or, (Re)reading The Making at UQAM" by Magda Fahrni; and "Individual Statements on E.P. Thompson" by, respectively, Jesse Lemisch, Alice Kessler-Harris, and June Hannam.
Keywords: MAKING of the English Working Class, The (Book); THOMPSON, E. P. (Edward Palmer), 1924-1993

E.P. Thompson's The Making of the English Working Class at Fifty - Palmer, Bryan D.; Merrill, Michael; Way, Peter; Loo, Tina; Levine, David; Hill, Rebecca; Cadigan, Sean; Jacob, Margaret C. (Labour / Le Travail, 2013)
The article introduces the first of a two-part series in the journal on the 50th anniversary of the publication of "The Making of the English Working Class" by British historian E.P. Thompson. In addition to describing their own responses, the authors discuss how the book has influenced working-class studies, its political impact, Thompson's Marxism, and his critique of Methodism. The articles in the presentation include: "E.P. Thompson’s Capital: Political Economy in The Making" by Michael Merrill; "Among the Autodidacts: The Making of E.P. Thompson" by Margaret C. Jacob; “The something that has called itself ‘Marxism’” by Peter Way; "The Face of Power" by Tina Loo; "A Definitive ‘And fookin’ Amen to that!" by David Levine; "Frame Breaking Then and Now" by Rebecca Hill; and "The Privilege of History" by Sean Cadigan.
Keywords: 20th century; LABOR movement -- History; MAKING of the English Working Class, The (Book); MARXIST philosophy; METHODISM; SOCIAL history -- 20th century; THOMPSON, E. P. (Edward Palmer), 1924-1993; WORKING class -- Research

Introduction: The Labour of Race - Park, Augustine S. J. (Canadian Journal of Sociology, 2013)
Special Issue Introduction: This special issue interrogates race as a labour. The “labor of race,” writes David Theo Goldberg in his book "The Threat of Race" (2009:4, emphasis in original), “is the work for which the category and its assumptions are employed to effect and rationalize social arrangements of power and exploitation, violence and expropriation.” Race, for Goldberg, is a “foundational code” that has been built by “racial thinkers,” that is “the day-laborers, the brick-layers, of racial foundations” (2009:4). Understanding race as a labour underscores the ontological unreality of race, which is now, of course, the constructivist orthodoxy in critical sociologies of race. In other words, conceptualizing race as a labour asserts race as an accomplishment, however unstable: an historical, social, economic, and cultural achievement that designates a constantly shifting political grammar. At the same time, understanding race as a labour, or the labour of race, demands that we ask to what work race is put. Following Zygmunt Bauman’s (2004) theorization of “wasted lives,” race might be theorized as a method of social ordering.

Life Among the Ruins: Deindustrialization in Historiographical Perspective - Parnaby, Andrew (Labour / Le Travail, 2013)
The article reviews and comments extensively on the book, "Industrial Ruination, Community, and Place: Landscapes and Legacies of Urban Decline" by Alice Mah.
Keywords: DEINDUSTRIALIZATION; INDUSTRIAL Ruination, Community & Place: Landscapes & Legacies of Urban Decline (Book); MAH, Alice; Nonfiction

All the People: Uncovering the Hidden History of Cooperation, Cooperative Movements, and Communalism in America - Patmore, Greg (Labour / Le Travail, 2013)
The article reviews the book, "For All the People: Uncovering the Hidden History of Cooperation, Cooperative Movements, and Communalism in America," by John Curl.
Keywords: COOPERATION -- History; CURL, John; FOR All the People: Uncovering the Hidden History of Cooperation, Cooperative Movements & Communalism in America (Book); Nonfiction

Unionism and Non-Union Employee Representation: The Interwar Experience in Canada, Germany, the US and the UK - Patmore, Greg (Journal of Industrial Relations, 2013)
The decline in trade union membership in a number of countries has led to concerns over a ‘representation gap’, where workers are deprived of a voice not only in regard to their workplace grievances, but also in regard to their contributions to productivity and the quality of working life. While a number of alternatives have been raised, including joint consultation and works councils, there are concerns that these alternatives may further weaken union organization by establishing rival forms of organization. This article examines the interwar experience with three types of workplace non-union employee representation in Canada, Germany, the US and the UK. Where management recognizes unions and unions actively ensure that they dominate these representation mechanisms, they can enhance union organization.
Keywords: Employee representation plans; Works councils; representation gap; union organization; works committees

Fort Chipewyan and the Shaping of Canadian History, 1788-1920s: "We like to be free in this country" - Payne, Michael (Labour / Le Travail, 2013)
The article reviews the book, "Fort Chipewyan and the Shaping of Canadian History, 1788-1920s: 'We like to be free in this country,'" by Patricia A. McCormack.
Keywords: Canada; FORT Chipewyan & the Shaping of Canadian History 1788-1920s: We Like to Be Free in This Country (Book); FUR trade; History; MCCORMACK, Patricia A.; Nonfiction

L'intervention en ergonomie - Petit, Johann (Relations industrielles / Industrial Relations, 2013)
The article reviews the book, "L’intervention en ergonomie," by Marie Saint-Vincent, Nicole Vézina, Marie Bellemare, Denys Denis, Élise Ledoux and Daniel Imbeau.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Judging Homosexuals: A History of Gay Persecution in Quebec and France - Pineault, Virginie (Labour / Le Travail, 2013)
The article reviews the book, "Judging Homosexuals: A History of Gay Persecution in Quebec and France," by Patrice Corriveau.
Keywords: CORRIVEAU, Patrice; Canada; EUROPE; Homophobia; JUDGING Homosexuals: A History of Gay Persecution in Quebec & France (Book); Nonfiction

The Psychology of Assessment Centers - Poropat, Arthur (Relations industrielles / Industrial Relations, 2013)
The Psychology of Assessment Centers, edited by Duncan J. R. Jackson, Charles E. Lance and Brian J. Hoffman, is reviewed.
Keywords: Assessment centers; Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Organization development; Psychological aspects; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Globalization, Restructuring and Unions: Transnational Co-ordination and Varieties of Labour Engagement - Pulignano, Valeria; Lucio, Miguel Martínez; Walker, Steve (Relations industrielles / Industrial Relations, 2013)
The structure, content and space of union transnational co-ordination are much richer and complex than simply revolving around tensions and relations between bureaucrats and local activists. This is illustrated through the ETUC TRACE project, a study of a managed and steered form of international union coordination. Drawing on this study, this paper discerns a form of co-ordination that worked across various dimensions of action (i.e. "influencing" politics and "communicating" policy), various political relations (internal and external relations) and different organizational levels (micro and macro). By adding original material to the existing literature, the paper stresses the relevance of the project and the various dimensions for appreciating the problems unions face in establishing and sustaining effective cross-national coordination and a supportive environment of "union learning". The TRACE project acknowledged the need to build coordination through a variety of means and serves as an invaluable insight and lesson into more managed and conscious forms of coordination.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Coordination; Globalization; Labor Unions; Management theory; Organizational learning; Project management; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

La colonie nantaise de Lac-Mégantic. Une implantation française au Québec au XIXe siècle - Pyée, Audrey (Labour / Le Travail, 2013)
The article reviews the book, "La colonie nantaise de Lac-Mégantic. Une implantation française au Québec au XIXe siècle," by Marcel Fournier.
Keywords: EMIGRATION & immigration; FOURNIER, Marcel; FRANCE; History; LA colonie nantaise de Lac-Megantic: Une implantation francaise au Quebec au XIXe siecle (Book); LAC-Megantic (Quebec); Nonfiction

Health And Safety For Canadian Youth In Trades - Raykov, Milosh; Taylor, Alison (Just Labour: A Canadian Journal of Work and Society, 2013)
This article examines occupational health and safety (OHS), with a particular focus on youth apprentices. It uses quantitative and qualitative data to examine the incidence of injuries among youth apprentices, and their experiences related to health and safety at work in Canada. Analysis of large-scale national surveys suggests a high incidence of work-related injuries among youth and low participation rates of younger workers in formal OHS training. A survey of 173 former Ontario Youth Apprenticeship Program (OYAP) and Registered Apprenticeship Program in Alberta (RAP) participants finds that one-fifth suffered serious occupational injuries, which required time off work. The results from this study have important implications for youth apprenticeship programs, particularly the OHS- and trade-specific knowledge required for youth to work safely during and following their apprenticeship training.

Constitutional Restrictions on the Capacity of Governments to Enact Reforms: Does Section 2(d) of the Charter Include a Right to Strike Prospects for Reform of Industrial Relations in the Ontario Broader Public Sector: Papers from the Workshop on the Drummond Report Centre for Law in the Contemporary Workplace, Queen's University, June 22, 2012 - Regenbogen, Sonia; Pigott, Christopher D. (Canadian Labour and Employment Law Journal, 2013)
This paper considers the likelihood of whether freedom of association under section 2(d) of the Charter will be held to include a constitutional right to strike - a question which the Supreme Court of Canada will have an opportun- ity to answer when it hears the upcoming appeal in the Saskatchewan Federation of Labour case. The authors note that the prospects for the recognition of such a right have changed dramatically in the five years since the Supreme Court concluded in B.C. Health that the Charter provided protection for a limited process of collective bargaining. The main reason for this shift is the Court's subsequent decision in the Fraser case, holding that collective bargaining is merely a "derivative right" of freedom of association and that an infringement of section 2(d) in the labour relations context will be found only where the impugned legislation or state action has the effect of making it "impossible" for employees to collectively pursue workplace goals. The authors go on to review how this "effective impossibility" test has been applied by appellate courts in Ontario, British Columbia and the federal jurisdiction in recent freedom of asso- ciation claims. In their view, the restrictive approach now taken by the courts makes it highly unlikely that section 2(d) will be found to protect a right to strike. Even if strike activity is held to attract constitutional protection, they argue, such protection would apply only in very limited situations.

Committing Theatre: Theatre Radicalism and Political Intervention in Canada - Rifkind, Candida (Labour / Le Travail, 2013)
The article reviews the book, "Committing Theatre: Theatre Radicalism and Political Intervention in Canada," by Alan Filewood.
Keywords: COMMITTING Theatre: Theatre Radicalism & Political Intervention in Canada (Book); Canada; FILEWOOD, Alan; History; Nonfiction; THEATER -- Political aspects; Theater

Boom, Bust and Crisis: Labour, Corporate Power and Politics in Canada - Robinson, Ian (Relations industrielles / Industrial Relations, 2013)
Boom, Bust and Crisis: Labour, Corporate Power and Politics in Canada, edited by John Peters, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Changes; Corporate culture; LABOR market; Labor Unions; Neoliberalism; Political economy; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Does Industrial Relations Research Support Policy? A Comparative Assessment of Research on Spain - Rohlfer, Sylvia (Relations Industrielles / Industrial Relations, 2013)
This article reviews the English-speaking literature on Spanish and German industrial relations published in the top 10 journals between 2000 and 2010. Our analysis contributes to the debate about the relevance of industrial relations by establishing the state of the art in research on Spain using Germany as a point of comparison. Apart from indicating deficiencies in research on Spain, the results reveal a greater convergence in research regarding its restricted multidisciplinary character, its focus on the international level and a strong emphasis on empirical, quantitative work with analysis conducted at various levels. At the same time some path dependency continues to exist, particularly concerning the active participants in research and the subjects for investigation. We conclude by discussing whether the research on Spain should require normative preconceptions in order to orient policymakers -- an aspect that has been largely overlooked when discussing the rejuvenation of industrial relations.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Comparative analysis; Convergence; Labor Unions; Labor relations; Policy making; Studies

Reforming the Structure of Collective Bargaining: Lessons from the Construction Industry Prospects for Reform of Industrial Relations in the Ontario Broader Public Sector: Papers from the Workshop on the Drummond Report Centre for Law in the Contemporary Workplace, Queen's University, June 22, 2012 - Rose, Joseph B. (Canadian Labour and Employment Law Journal, 2013)
One of the reforms proposed for Ontario's broader public sector by the Drummond Report is the establishment of centralized bar- gaining structures. As Chaykowski and Hickey have argued, such a reform "must consider whether, how, and in what context, alterna- tive bargaining structures and enhanced coordination could yield outcomes which promote efficiencies and improve value."' In this regard, the transformation of bargaining structures in the Canadian construction industry offers some lessons on structural realignment.

Boom, Bust and Crisis: Labour Corporate Power and Politics in Canada - Rosenfeld, Herman (Labour / Le Travail, 2013)
The article reviews the book, "Boom, Bust and Crisis: Labour Corporate Power and Politics in Canada," edited by John Peters.
Keywords: BOOM, Bust & Crisis: Labour, Corporate Power & Politics in Canada (Book); CANADA -- Economic conditions; Nonfiction; PETERS, John

"Just Business": 1970s Management Paternalism and Failed Service Sector Unionization - Russell, Jason (Labour / Le Travail, 2013)
[The article shows] how management in the post-war period – in this case [Hobbs Hardware in] the mid-1970s – orchestrated effective campaigns to keep low-wage workers out of unions. This is especially true for those workers who toiled in seemingly inconsequential workplaces that were part of the growing service sector, and where unionization was largely prevented. The fact that unionization did not expand into the service sector would have lasting consequences for workers in service industries, for class relations across sectors, and for the Canadian labour movement. [The] analysis utilizes archival documents, but also relies on the memories of three former Hobbs workers.... --From author's introduction
Keywords: ASHTON, Steve; HOBBS Hardware (Company); LABOR organizing; Management; Neoliberalism; PERKINS, Doug; PERKINS, Ed; Paternalism; SERVICE sector

Uneasy Allies: Working for Labor Reform in Nineteenth Century Boston - Ryan, Francis (Labour / Le Travail, 2013)
The article reviews the book, "Uneasy Allies: Working for Labor Reform in Nineteenth Century Boston," by David A. Zonderman.
Keywords: 19th century; BOSTON (Mass.); History; LABOR law reform; Nonfiction; UNEASY Allies: Working for Labor Reform in 19th-Century Boston (Book); ZONDERMAN, David A.

Oral History and Working Class History: A Rewarding Alliance - Sangster, Joan (Oral History Forum d'histoire orale, 2013)
Since the 1960s, if not before, oral history and working-class history have been a dynamic duo, complimenting and overlapping, but also challenging and questioning each other. Both lay and professional historians have been in the forefront of efforts to recuperate, interpret, and preserve the oral histories of working-class individuals and communities across the globe. They created written histories, archival collections, museum exhibits, and community projects that gave workers, their families, and their communities -- those who were less likely to leave archival and written sources for posterity -- a new voice, and a new place in history. Working-class oral history has also encompassed far more than recovery and preservation. Labour historians have enriched the field of oral history by addressing questions about method, theory, and approach, by offering critical reflections on our assumptions and expectations about oral history practice. Oral history has similarly enriched the field of working-class history, posing new questions, challenging existing interpretations, and encouraging the diversification of the themes and subjects we study. In recognition of this dynamic relationship, and the ongoing, mutually beneficial conversation between oral and working-class history, Oral History Forum commissioned this special issue. --Introduction

Ours to Master and to Own: Workers' Control from the Commune to the Present - Schmidt, Ingo (Labour / Le Travail, 2013)
The article reviews the book, "Ours to Master and to Own: Workers' Control from the Commune to the Present," edited by Dario Azzellini and Immanuel Ness.
Keywords: AZZELLINI, Dario; NESS, Immanuel; Nonfiction; OURS to Master & to Own: Workers' Control From the Commune to the Present (Book); WORKING class -- History

Social Integration and Workplace Industrial Relations: Migrant and Native Employees in German Industry - Schmidt, Werner; Müller, Andrea (Relations industrielles / Industrial Relations, 2013)
This article examines the social integration of migrant and native employees in German industrial workplaces and the impact of workplace industrial relations on it. Drawing on data from interviews with management, works councils and employees, employee surveys and company statistics from three manufacturing companies, it analyzes the positioning of employees of different origin within the companies' social structure, explores their social interaction and asks what role works councils play in fostering social integration of a heterogeneous workforce. Findings show that workplaces are not free from discrimination but, rather, "pragmatic cooperation" and collegiality prevail. It is argued that the legal framework of German co-determination and workplace actors' orientation towards universalistic rule application ("internal universalism") encourages individuals to constitute themselves as employees with common interests and foster social integration.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Impact analysis; Labor Unions; Labor relations; Manufacturers; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social integration; Social interaction; Studies; Workforce

Canada and the Second World War: Essays in Honour of Terry Copp - Sendzikas, Aldona (Labour / Le Travail, 2013)
The article reviews the book, "Canada and the Second World War: Essays in Honour of Terry Copp," edited by Geoffrey Hayes, Mike Bechtold, and Matt Symes.
Keywords: BECHTHOLD, Mike; CANADA & the Second World War: Essays in Honour of Terry Copp (Book); Canada; HAYES, Geoffrey; Nonfiction; SYMES, Matt; WORLD War, 1939-1945

In the Cause of Freedom: Radical Black Internationalism from Harlem to London 1917-1939 - Seniors, Paula Marie (Labour / Le Travail, 2013)
The article reviews the book, "In the Cause of Freedom: Radical Black Internationalism From Harlem to London 1917-1939," by Minkah Makalani.
Keywords: BLACKS -- Political activity; IN the Cause of Freedom: Radical Black Internationalism From Harlem to London 1917-1939 (Book); MAKALANI, Minkah; Nonfiction

Choice, Interrupted: Travel and Inequality of Access to Abortion Services since the 1960s - Sethna, Christabelle; Palmer, Beth; Ackerman, Katrina; Janovicek, Nancy (Labour / Le Travail, 2013)
Travel is one of many extra-legal barriers that restrict access to abortion services. Paradoxically, women travel at the international, domestic, and local levels to circumvent legal and/or extra-legal barriers to access. Through an examination of four specific Canadian responses to inequality of access to abortion services relative to shifts in the legal terrain from the 1960s onwards, the authors demonstrate that travel signifies an interruption to reproductive choice. Women went to Britain and the United States for an abortion when these countries relaxed their abortion legislation. Within Canada, women sought out the services offered by the Morgentaler Clinic in Montreal in order to avoid the abortion bureaucracy that limited their right to choose. In New Brunswick, the pro-life movement successfully lobbied hospitals to restrict abortion services, and the provincial government to deny funding for abortions performed in freestanding clinics, forcing women to travel to access abortion services. Pro-choice activists in southeastern British Columbia launched a successful campaign to protect hospital abortions, ensuring that rural women had access to abortion services within their home communities. Today, 25 years after the Supreme Court of Canada struck down the abortion law, abortion services are uneven at best and unattainable at worst in different regions of the country.
Keywords: Abortion; Canada; Hospitals; MEDICAL laws & legislation; MEDICAL tourism; PRO-choice movement; PRO-life movement; RURAL women; TRAVEL -- Health aspects; WOMEN'S health services; Women's rights

Gender Risk and Employment Pension Plans in Canada - Shilton, Elizabeth (Canadian Labour and Employment Law Journal, 2013)
Current policy debates about Canada's retirement income system have failed to consider "gender risk" - i.e. the risk that Canadian women will bear a disproportionate share of welfare loss in old age. This paper argues that the continuing gender disparity in retirement income reflects Canada's heavy reli- ance on private pension instruments generated and shaped by labour markets. The author begins by looking at the relationship between gender and Canada's three-pillar retirement income system, noting that while public pensions distrib- ute benefits based on explicit policy goals, private pensions distribute them based on the "hidden hand" of market principles. She then considers the differential impact of employment-based pension plans on men and women as a function of the distinct patterns of male and female engagement in the labour market. Noting the close relationship between pension design choices and gender outcomes, she goes on to discuss the pension reforms introduced by Canadian governments in the 1960s and 1980s, in which those governments saw gender inequality as an issue to be addressed primarily by mandatory public plans rather than by voluntary private plans. Ultimately, the author contends, the gendered impact of Canada's pension system flows from the complex interaction between women's paid employment and their reproductive and caregiving work. A gender-equal pension system would recognize the unequal burden borne by women in labour markets and in families, and would pool and share the welfare risks which that inequality entails. Voluntary employment-based pension plans shaped by market imperatives at the enterprise level will not address these issues, in the author's view, nor will the type of individualized pension contemplated by the federal government's recent PRPP legislation providing for pooled savings vehicles to which employers do not contribute. What is needed, she argues, is a broad- based collective risk-sharing vehicle such as the CPP/QPP.

Last Nightshift in Savar: The Story of the Spectrum Sweater Factory Collapse - Spencer, Bruce (Relations industrielles / Industrial Relations, 2013)
The article reviews the book, "Last Nightshift in Savar: The Story of the Spectrum Sweater Factory Collapse," by Doug Miller.
Keywords: Book reviews; Building failures; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Factories; Fatalities; Labor Unions; Labor standards; Multinational corporations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Moving Beyond Borders: A History of British Canadian and Caribbean Women in the Diaspora - Springfield, Consuelo Lopez (Labour / Le Travail, 2013)
The article reviews the book, "Moving Beyond Borders: A History of British Canadian and Caribbean Women in the Diaspora," by Karen Flynn.
Keywords: Diaspora; FLYNN, Karen; MOVING Beyond Borders: A History of Black Canadian & Caribbean Women in the Diaspora (Book); Nonfiction

Remembering and Forgetting Winnipeg: Making History on the Strike of 1919 - Stace, Trevor (Constellations, 2013)
This article examines the approaches that historians, beginning in the mid 20th century and into the early 21st century, used to write about the Winnipeg General Strike of 1919. It focuses on five major works: "The Winnipeg General Strike" by D.C. Masters; "Confrontation at Winnipeg" by David J. Bercuson; "The Workers' Revolt in Canada, 1917-1925" edited by Craig Heron; and "When the State Trembled: How A.J. Andrews and the Citizens' Committee Broke the Winnipeg General Strike" by Tom Mitchell and Reinhold Kramer. It identifies where the monographs depart from one another in interpretation; as well as where they remain the same. Given the layers of complexity, the interpretation of the event becomes especially salient in the 21st century as its 100th anniversary steadfastly approaches and the question of how should it be publicly presented in 2019 requires an answer soon (which the paper also addresses).

Employee Rights and Employer Wrongs: How to Identify Employee Abuse and How to Stand Up for Yourself - Stacey, Kent (Relations industrielles / Industrial Relations, 2013)
Employee Rights and Employer Wrongs: How to Identify Employee Abuse and How to Stand Up for Yourself, by Suzanne Kleinberg and Michael Kreimeh, is reviewed.
Keywords: Absenteeism; Antisocial personality disorder; Book reviews; Bullying; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Participation financière et climat social : une analyse des perceptions comparées dirigeants/salariés - Stévenot, Anne; Guery, Loris (Relations industrielles / Industrial Relations, 2013)
L’article s’interroge, dans la perspective de l’institutionnalisme économique de Commons, sur la relation unissant les dispositifs de participation financière au climat social, appréhendé par le biais de la perception qu’en ont les dirigeants et les salariés, d’une part, et par des indicateurs de dysfonctionnements sociaux, tels que l’absentéisme et les conflits sociaux, d’autre part. La question des caractéristiques de ces pratiques (modalités de négociation présidant à leur mise en oeuvre, types de dispositifs, mode de calcul) est également posée. L’étude empirique est fondée sur l’exploitation de l’enquête REPONSE qui représente un échantillon de 3 000 établissements français et de 8 000 salariés. Au-delà des différences de perception entre dirigeants et salariés, les résultats, obtenus à l’aide de modèles de régressions logistiques, mettent tout d’abord en évidence que plus que le montant versé, c’est l’existence même d’un dispositif de participation financière qui influence le climat social. Par ailleurs plus les dispositifs apparaissent comme désintéressés de la part de l’entreprise et meilleur est le climat social du point de vue des salariés. Les modalités de conclusion de l’accord de participation financière, notamment l’intervention des syndicats, ont également une influence sur le climat social. Compte tenu des différences de résultats pouvant exister selon que l’on s’intéresse à la perception des dirigeants, à celle des salariés ou aux indicateurs de dysfonctionnements sociaux, l’article met également en lumière l’importance pour les recherches sur le climat social de prendre en compte à la fois les dimensions objectives du climat social et la perception qu’en ont les acteurs.
Keywords: ahorro salarial; clima de trabajo; climat de travail; employee savings; intéressement; participación en los beneficios; profit-sharing; remuneración; remuneration; rémunération; work atmosphere; épargne salariale

The Labour Geographies of Education: The Centralization of Governance and Collective Bargaining in Ontario, Canada - Sweeney, Brendan (Geoforum, 2013)
Labour geography has yet to pay full attention to the experiences of public sector workers and their employer (the state). This article addresses this lacuna and provides some insight into the labour geographies of public sector workers through an empirical analysis of the centralization of governance, employment relations, and collective bargaining in Ontario, Canada’s publicly-funded elementary and secondary schools. This case demonstrates how one particular group of public sector workers – teachers – and their unions located and exercised agency in the arenas of politics and collective bargaining through a rescaling of their activities from the local to the provincial level. The paper also argues that the rescaling of politics and collective bargaining is problematic. Questions remain regarding whether or not Ontario’s teachers were able to increase their aggregate bargaining power through centralization or merely transferred agency and authority from one scale to another. Moreover, the paper engages with the fast-developing geographies of education literature, and is consistent with an outward-looking approach that links education to wider political and economic processes. In so doing, it extends the scope of the geographies of education to the employees of publicly-funded schools and their administrative bodies, and suggests value a theoretically- and empirically-informed dialogue between geographers interested in education and those interested in labour.
Keywords: Canada; Collective bargaining; Education; Labour; Rescaling; Teachers

The Relative Role of Safety and Productivity in Canadian Ergonomists' Professional Practices - Theberge, Nancy; Neumann, W. Patrick (Relations industrielles / Industrial Relations, 2013)
This article examines the professional practices of a sample of 21 Canadian ergonomists from across Canada, focusing on the manner in which they report negotiating the intersection of safety and productivity in their work. Results indicate that ergonomic practice is directed primarily to safety concerns. A minority of study participants addressed productivity concerns, either as secondary or primary outcomes of ergonomic applications. In either instance, efforts to highlight the contribution of ergonomics to production did not significantly disrupt the dominant safety oriented perception of the field. Financial considerations were major determinants of whether recommendations were implemented. An irony of the dominant understanding of ergonomics as oriented to safety, with little reference to performance aspects, is that this provides the main basis for its growing presence in workplaces but also limits its applications.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Ergonomics; Labor Unions; Occupational hazards; Occupational safety; Productivity; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

La précarisation du travail : des parcours professionnels à géométrie variable - Thirot, Myriam (Relations industrielles / Industrial Relations, 2013)
Le développement des emplois « atypiques » au Québec donne lieu à la mise en évidence de nouveaux enjeux sociaux et politiques dans un contexte de flexibilité de la main-d’oeuvre. La segmentation du marché du travail qui en découle se caractérise par une précarisation du salariat, définie comme un processus structurel de détérioration des conditions de travail et d’emploi. La sociologie s’intéresse particulièrement aux conséquences de ces mutations sur les conditions de vie à travers l’analyse des perceptions subjectives des acteurs concernés. Ainsi, le rapport au travail incluant les conditions matérielles, l’accomplissement des tâches et la socialisation comporte une dichotomie articulée autour de la satisfaction du salarié, source de valorisation ou de la non-satisfaction, entraînant un mal-être. Les transformations récentes du monde du travail construisent des parcours professionnels morcelés et incertains et nécessitent une réévaluation de leurs impacts sur ce rapport, encore peu documentée. Que signifie occuper un emploi atypique pour ces travailleurs ? La valeur associée au travail est-elle remise en cause ? Les indices contenus dans leurs parcours professionnels constituent-ils une réalité nouvelle ? Basé sur les résultats d’une recherche qualitative menée en 2009 auprès de résidents d’un quartier défavorisé du centre-ville de Montréal, ayant occupé des emplois « atypiques », cet article permet d’entrer au coeur des dynamiques relationnelles des milieux de travail québécois, de comprendre en quoi elles participent à la construction de parcours professionnels spécifiques et d’identifier leurs conséquences sur le rapport au travail et à l’emploi de ces travailleurs. Les différentes expériences étudiées apportent un éclairage sur le phénomène de la précarisation du travail et suggèrent des perspectives tant scientifiques que politiques.
Keywords: desigualdades sociales; inégalités sociales; life course; parcours de vie; precarización del trabajo; précarisation du travail; social inequality; sociologie compréhensive; sociology; sociología comprensiva; trayectorias de vida; work precariousness

Making it Like a Man: Canadian Masculinities in Practice - Thorn, Brian (Labour / Le Travail, 2013)
The article reviews the book, "Making It Like a Man: Canadian Masculinities in Practice," edited by Christine Ramsay.
Keywords: MAKING It Like a Man: Canadian Masculinities in Practice (Book); Masculinity; Nonfiction; RAMSAY, Christine

The Assessment of Reasonable Notice by Canadian Appellate Courts from 2000 to 2011 - Thornicroft, Kenneth Wm. (Canadian Labour and Employment Law Journal, 2013)
Canadian employers have a common law obligation to give reasonable notice when terminating an employment relationship without cause. In deter- mining the appropriate length of the notice period, trial judges hearing wrongful dismissal claims must consider a range of factors, including what are known as the Bardal factors. In this paper, the author presents and analyzes the results of his empirical study of appeal court decisions reviewing trial court awards of reasonable notice across Canada from 2000 to 2011, and examines the impact of the Bardal factors (as well as several others) on outcomes at the appellate level. The study finds that appeal courts have not treated all of the Bardal factors equally, but appear to have given the most weight to the employee's age and length of tenure. Other factors found to have significant predictive value on the length of reasonable notice awards were the employee's gender and whether a successful claim for Wallace damages was made. The data also indicate that employee appeals have succeeded relatively more often than employer appeals, and that the length of notice ordered by appellate courts seems to have plateaued over time. In light of his conclusion that only a narrow range of considerations significantly affect notice awards, the author argues that the current system of judicial assessment of reasonable notice could well be replaced by a less expen- sive and time-consuming statutory scheme that would incorporate a formula for applying the relevant factors and would be administered by employment standards tribunals rather than by the courts.

Race on Trial: Black Defendants in Ontario's Criminal Courts, 1858-1958 - Toney, Jared G. (Labour / Le Travail, 2013)
The article reviews the book, "Race on Trial: Black Defendants in Ontario's Criminal Courts, 1858-1958," by Barrington Walker.
Keywords: BLACKS -- Legal status, laws, etc.; DEFENDANTS; Nonfiction; RACE on Trial: Black Defendants in Ontario's Criminal Courts 1858-1958 (Book); WALKER, Barrington

Les temporalités dans les sciences sociales - Tremblay, Diane-Gabrielle (Relations industrielles / Industrial Relations, 2013)
The article reviews the book, "Les temporalités dans les sciences sociales," edited by Claude Dubar and Jens Thoemmes.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Retour sur les origines du mouvement ouvrier québécois: profil et aspirations des militants syndicaux et démocrates durant les années 1830 - Tremblay, Robert (Labour/Le Travail, 2013)
Cet article, qui se veut à la croisée des chemins entre une démarche prosopographique et une approche d’histoire sociale, entend examiner des logiques jusqu’à maintenant inexplorées au sein du monde ouvrier bas-canadien des années 1830. C’est ainsi qu’à partir d’un portrait d’ensemble de quelque quatre-vingts militants ouvriers de la première heure, nous tenterons de poser certains éléments nouveaux de réflexion sur cette période tourmentée de notre histoire. Quelle lecture pouvons-nous faire des divers fragments de vie d’ouvriers québécois engagés dans des actions syndicales et revendicatives durant les années 1830? En quoi leur expérience est-elle révélatrice d’un milieu social à cheval entre la tradition et la modernité? D’ores et déjà, nous pouvons dire que ces premiers militants sont issus généralement de métiers (typographes, cordonniers, tailleurs d’habits, charpentiers-menuisiers, etc.), dont le cadre normatif d’ascension professionnelle était particulièrement menacé par l’avènement du marché capitaliste du travail et par les premières tentatives de rationalisation du travail en manufacture. Outre le fait d’avoir rendu possible la personnification des gestes et de la parole ouvrière, cette recherche a révélé la diversité et la polyvalence des engagements ouvriers (syndicats, coopératives, sociétés de secours mutuel, associations civiques antimonopole, etc.) durant la période, de même que le rôle primordial joué par les bourses ouvrières du travail, en vue de contrôler l’offre en main-d’oeuvre dans les villes, et l’importance de l’idéologie du républicanisme ouvrier auprès des classes populaires. Grâce à ce riche matériel biographique, nous avons été également en mesure de découvrir l’étonnante ambivalence du monde ouvrier face au mouvement patriote et réformiste des années 1830.
Keywords: 19th century; CAPITALISM -- History; Canada; Capitalism; Commerce; Equality; History; INDUSTRIALIZATION -- History; LABOR activists; LABOR movement -- History; Politics & government; QUEBEC (Province); Radicalism; WORKING class -- Political activity

A Life in Balance? Reopening the Family-Work Debate - Troup, Carolyn (Relations industrielles / Industrial Relations, 2013)
A Life in Balance? Reopening the Family-Work Debate, edited by Catherine Krull and Justyna Sempruch, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Stereotypes; Women; Work life balance

The Great Industrial War: Framing Class Conflict in the Media, 1865-1950 - Trutor, Clayton (Labour / Le Travail, 2013)
The article reviews the book, "The Great Industrial War: Framing Class Conflict in the Media, 1865-1950," by Tony Rondinone.
Keywords: GREAT Industrial War: Framing Class Conflict in the Media 1865-1950, The (Book); History; Industrial relations; Nonfiction; RONDINONE, Tony; United States; Working class

Rebuilding Professional Lives: Immigrant Professionals Working in the Ontario Settlement Service Sector - Türegün, Adnan (Journal of International Migration and Integration, 2013)
Based on an online survey and in-depth interviews conducted from 2009 to 2010, this study looks at the reality of a particular group of foreign-born and foreign-trained professionals in Ontario. These are the professionals who did not get to practise their respective professions after immigration but acquired a new profession in the form of settlement work. The study identifies their pre-immigration education and work history, the reasons they left their countries of origin (or of permanent residence) for Canada, the expectations they had, the choices they made about pursuing professional practice, the efforts they put towards that or some alternative goal, and their eventual professional reconstitution as settlement workers. Following the Canadian trajectory of these dual professionals has three contributions to research into immigrant access to professions. First, their individual experiences reveal the social processes of inclusion in, and exclusion from, professional practice. Second, unlike those immigrants who are de-professionalized in the post-immigration period, our target population reinvent themselves as practitioners of a new profession and thus provide a more nuanced immigrant experience. Third, their common practice as settlement workers gives us insight into the dynamics of an emerging profession that is settlement work.
Keywords: Demography; Immigrant access to professions and trades; Migration; Population Economics; Professionalization of settlement work; Recognition of foreign credentials; Settlement workers; Sociology, general

The Smelter Poets: The Inspiring Role of Worker Poetry in a BC Labour Newspaper during the" Age of the CIO [Congress of Industrial Organizations]" - Verzuh, Ron (BC Studies: The British Columbian Quarterly, 2013)
When celebrated Wobbly troubadour Joe Hill purportedly visited the Rossland Miners’ Hall in the early 1900s to lend his support to the first Canadian local of the rugged Western Federation of Miners (WFM), he no doubt shared some of his inspired verses with the mine workers who are said to have protected him. Claims of his visit are unsubstantiated, but if he did get to Rossland, British Columbia, he likely would have sung them some of his most popular tunes about struggle, resistance, and the dream of a workers’ paradise, and in so doing he would have been performing the same service that poets and songwriters had rendered working people since the earliest days of the trade union movement. This paper explores examples of that historical literary tradition through a study of smelter worker poetry found in the pages of The Commentator, a trade union newspaper published in Trail by Local 480 of the International Union of Mine, Mill and Smelter Workers (Mine Mill) in the late 1930s and early 1940s as labour activists were striving to rekindle the union spirit at the Consolidated Mining and Smelting Company of Canada (CM&S Company), then the world’s largest lead and zinc smelter and a key munitions manufacturer during the First and Second World Wars.
Keywords: Trail

Poverty in Common: The Politics of Community Action During the American Century - Vibert, Elizabeth (Labour / Le Travail, 2013)
The article reviews the book, "Poverty in Common: The Politics of Community Action During the American Century," by Alyosha Goldstein.
Keywords: GOLDSTEIN, Alyosha; Nonfiction; POLITICAL participation; POVERTY in Common: The Politics of Community Action During the American Century (Book)

“Rights without Remedies”: Enforcing Employment Standards in Ontario by Maximizing Voice among Workers in Precarious Jobs - Vosko, Leah (Osgoode Hall Law Journal, 2013)
Workers in Ontario, Canada are on the edge of a crisis in the enforcement of their minimum employment standards (ES). This crisis is shaped not only by well-documented deficiencies in the scope of labour protection but by the fact that the administration of the ES system has not kept pace with the increasing number of workers and workplaces requiring protection under the province’s employment standards act. Coupled with an outmoded complaint-based system, the dearth of support for ES enforcement is cultivating a situation in which an unprecedented number of workers are bearers of rights without genuine opportunities for redress. Responding to this situation, this article explores how measures augmenting the voices of workers and their advocates could contribute to improving ES enforcement in Ontario. It does so through a review of innovative practices in other common law contexts characterized by similar enforcement regimes where labour market conditions have likewise deteriorated.

Physician Coping Styles and Emotional Exhaustion - Wallace, Jean E.; Lemaire, Jane (Relations industrielles / Industrial Relations, 2013)
This paper explores how coping styles relate to physicians' feelings of emotional exhaustion, a key dimension of burnout. We also explore whether four coping styles are more or less effective depending on certain dispositional and/or situational factors. We analyze survey data from 1,110 physicians in Western Canada. Denial is significantly related to physicians' emotional exhaustion, but it increases rather than decreases it. Physicians use denial when they experience work overload and difficult patient interactions. Furthermore, it is used by those with high negative affectivity. A highly positive outlook, however, appears to neutralize the harmful relationship between denial and emotional exhaustion. The harmful experiences related to stressful patient interactions are weakened for doctors who disengage or take a time out from the situation. We conclude that certain coping strategies are more effective depending on personality type and the type of stress encountered.
Keywords: Burnout; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Fatigue; Labor Unions; Occupational stress; Organizational behavior; Personality traits; Physicians; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

The Man Who Never Died: The Life, Times, and Legacy of Joe Hill, American Labor Icon - Wallace, Len (Labour / Le Travail, 2013)
The article reviews the book, "The Man Who Never Died: The Life, Times, and Legacy of Joe Hill, American Labor Icon," by William M. Adler.
Keywords: ADLER, William M.; HILL, Joe, 1879-1915; MAN Who Never Died: The Life, Times & Legacy of Joe Hill, American Labor Icon, The (Book); Nonfiction

Regulating the British Economy, 1660-1850 - Wallis, Patrick (Labour / Le Travail, 2013)
The article reviews the book, "Regulating the British Economy, 1660-1850," edited by Perry Gauci.
Keywords: Economic policy; GAUCI, Perry; GREAT Britain; History; Nonfiction; REGULATING the British Economy 1660-1850 (Book)

The Decline of Unionization in the United States: Some Lessons from Canada - Warner, Kris (Labor Studies Journal, 2013)
This article examines the decline in unionization that has occurred in the United States over the past half century, focusing on the role that employer opposition to unions has played, together with relatively weak labor law. It compares the U.S. experience and labor law regime to those of Canada. It finds that, compared to their Canadian counterparts, U.S. workers have much more difficulty in exercising their right to freely join and form unions and participate in collective bargaining, in large part due to ill-restrained employer opposition.
Keywords: Canada; Unionization; United States; card-check certification; first contract arbitration

Love the Questions: University Education and Enlightenment - Whiteley, Robert (Labour / Le Travail, 2013)
The article reviews the book, "Love the Questions: University Education and Enlightenment," by Ian Angus.
Keywords: ANGUS, Ian; LOVE the Questions: University Education & Enlightenment (Book); Nonfiction; UNIVERSITIES & colleges

The Bonds of Debt: Borrowing Against the Common Good - Williams, Brett (Labour / Le Travail, 2013)
The article reviews the book, "The Bonds of Debt: Borrowing Against the Common Good," by Richard Dienst.
Keywords: BONDS of Debt: Borrowing Against the Common Good, The (Book); DEBT; DIENST, Richard; Nonfiction; Social aspects

Evaluating the Prevalence and Distribution of Quasi-formal Employment in Europe - Williams, Colin C.; Padmore, Jo (Relations industrielles / Industrial Relations, 2013)
To show how formal and informal jobs are not always discrete, this paper uncovers how many formal employees in the European Union are paid two wages by their formal employers, an official declared salary and an additional undeclared wage, thus allowing employers to evade their full social insurance and tax liabilities. Analyzing a 2007 Eurobarometer survey involving 26,659 face-to-face interviews in the 27 member states of the European Union (EU-27), one in 18 formal employees are found to engage in such quasi-formal employment, receiving on average one-quarter of their gross salary on an undeclared basis. Multi-level logistic regression analysis reveals that quasi-formal employment is significantly more prevalent in East-Central Europe, in smaller businesses and the construction sector, and amongst men, younger persons and the lower paid. The paper then briefly reviews what might be done to tackle this illegitimate wage practice.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Employment; Labor Unions; Regression analysis; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Tax evasion; Wages & salaries